Gas barrier film and method for producing same
Patent Information
- Application Number
- JP2022504993
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-19
- Filing Date
- 2020-12-25
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-25
AI Technical Summary
【0011】 本開示のガスバリア性フィルムによれば、酸素バリア性皮膜の厚みが薄くても、製造ロット間での性能ばらつきが少なく、本来の酸素バリア性を安定して発現することで、優れたガスバリア性を発揮することができ、かつ、印刷適性を良好にできる。
Smart Images

Figure 0007632451000012 
Figure 0007632451000013 
Figure 0007632451000014
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a gas barrier film and a method for producing the same. [Background technology]
[0002] Packaging materials used for packaging food, medicine, etc. are required to have the property of preventing the intrusion of gases (water vapor, oxygen, etc.) that denature the contents, in order to prevent deterioration or spoilage of the contents and to maintain their function and quality. For this reason, film materials with gas barrier properties (gas barrier films) are used for these packaging materials.
[0003] As a gas barrier film, one in which a gas barrier layer made of a material having gas barrier properties is provided on the surface of a resin substrate is known. As a gas barrier layer, a metal foil, a metal vapor deposition film, and a film formed by a wet coating method are known. As a film that exhibits oxygen barrier properties, a resin film formed from a coating agent containing a resin such as a water-soluble polymer and polyvinylidene chloride, and an inorganic layered mineral composite resin film formed from a coating agent containing a water-soluble polymer and an inorganic layered mineral are known (Patent Document 1). Furthermore, as a gas barrier layer, a gas barrier layer in which a vapor deposition thin film layer made of an inorganic oxide and a gas barrier composite coating containing a water-soluble polymer, an inorganic layered compound, and a metal alkoxide are sequentially laminated (Patent Document 2), and a gas barrier layer containing a polyvalent metal salt of a carboxylic acid, which is a reaction product of a carboxy group of a polycarboxylic acid polymer and a polyvalent metal compound (Patent Document 3) have been proposed.
[0004] In order to improve the gas barrier property, for example, Patent Document 4 proposes a gas barrier film in which a coating is formed on at least one surface of a substrate, and the surface roughness parameter Rt / Ra of the coating surface is 20 or less. Here, Rt is the distance between the maximum peak and the deepest valley of the surface roughness curve, and Ra is the center line average roughness. The gas barrier film of Patent Document 4 aims to improve the gas barrier property. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6191221 [Patent Document 2] JP 2000-254994 A [Patent Document 3] Patent No. 4373797 [Patent Document 4] Japanese Patent Application Publication No. 9-150484 Summary of the Invention [Problem to be solved by the invention]
[0006] However, gas barrier films in which a coating is provided on the surface of a resin substrate by a wet coating method, a vapor deposition method, or a sputtering method sometimes have unstable oxygen barrier properties depending on the production lot. Specifically, the oxygen barrier properties of the gas barrier film are sometimes inferior to the inherent oxygen barrier properties, that is, the oxygen barrier properties expected from the material constituting the coating and the thickness of the coating. In particular, such problems tend to occur easily when the coating thickness is thin. Therefore, it is necessary to deal with this by making the gas barrier layer thicker than necessary, which causes problems such as poor productivity and excessive material costs.
[0007] Furthermore, the surface of the gas barrier film may be printed, and therefore the gas barrier film is required to have a surface that is easy to print on (printability).
[0008] The present disclosure has been made in consideration of the above circumstances, and aims to provide a gas barrier film that fully exhibits its inherent oxygen barrier properties, exhibits excellent gas barrier properties, and has good printability, even when the thickness of a coating for imparting oxygen barrier properties is thin, and a method for producing the same. [Means for solving the problem]
[0009] Gas barrier properties according to the present disclosurefilm The present invention comprises a resin substrate, an oxygen barrier coating film provided on at least one surface of the resin substrate, and either or both of an undercoat layer and an inorganic oxide layer provided between the resin substrate and the oxygen barrier coating film, and the one surface of the resin substrate has a black area ratio of 0.15% or less as measured by the following measurement method. <Measurement method> An arbitrary 1281 μm square area on one side of the resin substrate was photographed with an optical microscope to obtain a 1024 x 1024 pixel image. The photographed image was converted into a monochrome image with 256 gradations using image analysis software. The threshold value was determined by subtracting 30 from the most frequent brightness value in the monochrome image. Brightness was binarized with values below the threshold as black and values above the threshold as white. 2 The ratio of the total area of black areas of this size or larger is defined as the black area ratio.
[0010] The method for producing a gas barrier film according to the present disclosure includes the steps of measuring the black area ratio of the surface of a resin substrate raw sheet by the above-mentioned measuring method, preparing a resin substrate raw sheet having a black area ratio of 0.15% or less on at least one side as a resin substrate, and applying a coating agent to at least one side of the resin substrate to form at least an oxygen barrier film. Effect of the Invention
[0011] According to the gas barrier film of the present disclosure, even if the oxygen barrier coating is thin, there is little variation in performance between production lots and the inherent oxygen barrier properties are stably expressed, thereby enabling the film to exhibit excellent gas barrier properties and good printability. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view of the gas barrier film of the first embodiment. [Diagram 2] FIG. 2 is an image of one surface of the resin substrate of the first embodiment photographed with an optical microscope. [Diagram 3] FIG. 3 is an example of a histogram used to calculate the black area ratio. [Figure 4] FIG. 4 is a cross-sectional view of the gas barrier film of the second embodiment. [Diagram 5] FIG. 5 is a schematic diagram illustrating a measuring device for measuring the number of protrusions on the first surface of the resin substrate. [Figure 6] FIG. 6 is a schematic diagram for explaining the principle of detecting a protrusion portion. [Figure 7] FIG. 7 shows a photographed image of the first surface of the resin substrate of the example, and an analysis image showing protrusions detected from the photographed image. [Figure 8] FIG. 8 is a cross-sectional electron microscope image taken with a focused ion / electron beam processing and observation device, which shows the occurrence of coating defects in the locations of the resin substrate where the AB agent is present. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Embodiment 1) In order to investigate the cause of the above problem, the inventors of the present invention closely observed the surface and cross section of the gas barrier film with poor oxygen barrier properties using an optical microscope and an electron microscope. As a result of performing cross-sectional electron microscope observation using a focused ion / electron beam processing observation device at a portion where an antiblocking agent (hereinafter also referred to as "AB agent"), which is added to prevent blocking of the resin substrate, is present, it was confirmed that defects several μm wide occurred in the film at the portion where the AB agent protruded highly. It is believed that these defects became a path for gas permeation, and thus the oxygen barrier properties were not fully expressed.
[0014] The surface of the resin substrate has protrusions of various sizes due to the AB agent. The protrusion height and density of the AB agent vary depending on the production lot of the resin substrate. When the surface of the resin substrate is coated with a gas barrier film, the film is not formed locally at the positions of the large protrusions, resulting in defects and unstable oxygen barrier properties.
[0015] Furthermore, by closely examining the transfer failure of fine dots (sometimes called missing dots) that occurs in the highlight printed areas of the gas barrier film using a microscope, it was confirmed that missing dots are more likely to occur in areas where the AB agent protrudes highly.
[0016] Therefore, the present inventors have devised a method for quickly and accurately grasping the surface condition of a wide range of a resin substrate, which affects the oxygen barrier property and printability of a gas barrier film, and have performed binarization processing of an optical microscope image of the surface of the resin substrate to obtain a 100 μm 2 It was discovered that when the total area ratio of the black regions (hereinafter referred to as the black area ratio) is 0.15% or less, the oxygen barrier performance is excellent and the printability on the gas barrier film is good, which led to the present disclosure.
[0017] The gas barrier film of the present disclosure will be described with reference to an embodiment.
[0018] Fig. 1 is a schematic cross-sectional view of a gas barrier film 1 according to embodiment 1. For the sake of convenience, the dimensional ratio in Fig. 1 differs from the actual one.
[0019] The gas barrier film 1 comprises a resin substrate 10, an underlayer 30, an inorganic oxide layer 40, and an oxygen barrier coating 20. Either the underlayer 30 or the inorganic oxide layer 40 may be omitted.
[0020] The underlayer 30 is laminated in contact with one surface 12 of the resin substrate 10, and the inorganic oxide layer 40 is laminated on the surface of the underlayer 30 opposite to the surface in contact with the resin substrate 10. The inorganic oxide layer 40 is laminated in contact with the underlayer 30, and the oxygen barrier film 20 is located in contact with the surface of the inorganic oxide layer 40 opposite to the surface in contact with the underlayer 30. If the underlayer 30 is not provided, the inorganic oxide layer 40 is laminated on one surface 12 of the resin substrate 10. If the inorganic oxide layer 40 is not provided, the oxygen barrier film 20 is laminated on the underlayer 30.
[0021] <Resin substrate> The resin substrate 10 includes a resin. Examples of the resin constituting the resin substrate 10 include olefin-based resins such as polyethylene, polypropylene, polymers of olefins having 2 to 10 carbon atoms, and propylene-ethylene copolymers; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamide-based resins such as aliphatic polyamides such as nylon 6 and nylon 66, and aromatic polyamides such as polymetaxylylene adipamide; vinyl-based resins such as polystyrene, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyvinyl alcohol, and ethylene-vinyl alcohol copolymer; acrylic-based resins such as homopolymers or copolymers of (meth)acrylic monomers such as polymethyl methacrylate and polyacrylonitrile; cellophane; and engineering plastics such as polycarbonate and polyimide. These resins may be used alone or in combination of two or more.
[0022] Examples of the resin substrate 10 include a single-layer film made of a single resin, and a single-layer or laminated film made of multiple resins. A laminated substrate in which the above-mentioned resin is laminated on another substrate (metal, wood, paper, ceramics, etc.) may also be used. The resin substrate 10 may be a single layer or two or more layers. Examples of the resin substrate 10 that are preferred are polyolefin-based resin films (particularly, polyethylene films, polypropylene films, etc.), polyester-based resin films (particularly, polyethylene terephthalate-based resin films), polyamide-based resin films (particularly, nylon films), etc.
[0023] The resin substrate 10 may be an unstretched film or a uniaxially or biaxially stretched oriented film. From the viewpoint of excellent water vapor barrier properties, the resin substrate 10 is preferably a polyethylene film or a polypropylene film, and particularly preferably a biaxially stretched polypropylene film (OPP). The OPP may be at least one polymer selected from homopolymers, random copolymers, and block copolymers processed into a film. The homopolymer is a polypropylene consisting of only simple propylene. The random copolymer is a polypropylene in which the main monomer propylene and a small amount of a comonomer different from propylene are randomly copolymerized to form a homogeneous phase. The block copolymer is a polypropylene in which the main monomer propylene and the above comonomer are copolymerized in a block manner or polymerized into a rubber-like form to form a heterogeneous phase. When the resin substrate 10 is an OPP, the OPP may be one layer or two or more layers.
[0024] One surface 12 of the resin substrate 10 may be subjected to a surface treatment such as chemical treatment, solvent treatment, corona treatment, low-temperature plasma treatment, or ozone treatment in order to improve adhesion to the undercoat layer 30 or the inorganic oxide layer 40.
[0025] The resin substrate 10 may contain additives such as a filler, an antiblocking agent, an antistatic agent, a plasticizer, a lubricant, an antioxidant, etc. These additives may be used alone or in combination of two or more kinds.
[0026] When the resin substrate 10 contains an antiblocking agent (hereinafter also referred to as "AB agent"), unevenness resulting from the AB agent is formed on one surface 12 of the resin substrate 10. By containing the AB agent, the resin substrate 10 can impart convexities to the surface of the resin substrate 10, thereby suppressing the occurrence of blocking of the film. That is, by containing the AB agent in the resin substrate 10, the blocking resistance of the film can be increased. Therefore, the film can be easily wound up, and the processing characteristics of the film can be improved. Therefore, it is preferable that the resin substrate 10 contains the AB agent. On the other hand, if large convexities are formed on one surface 12 of the resin substrate 10, defects that become paths for gas permeation are likely to occur in the undercoat layer 30, inorganic oxide layer 40, and oxygen barrier film 20 formed thereon. Therefore, there is a risk that the oxygen barrier properties of the gas barrier film 1 will be reduced.
[0027] When the resin substrate 10 contains an AB agent, the AB agent is dispersed in the resin substrate 10. A plurality of protrusions derived from the AB agent are locally present on one surface 12 or the other surface 14 of the resin substrate 10. On one surface 12 and the other surface 14, the AB agent may be exposed or may be covered with a resin.
[0028] The AB agent is a solid particle, and examples thereof include organic particles and inorganic particles. Examples of the organic particles include polymethyl methacrylate particles, polystyrene particles, and polyamide particles. These organic particles are obtained, for example, by emulsion polymerization or suspension polymerization. Examples of the inorganic particles include silica particles, zeolite, talc, kaolinite, and feldspar. Any one of these AB agents may be used alone, or two or more of them may be used in combination.
[0029] The average particle size of the AB agent is preferably, for example, 0.1 to 5 μm in consideration of the appearance, transparency, possibility of the AB agent falling off, and anti-blocking performance of the gas barrier film 1. The average particle size of the AB agent is the weight average diameter measured by the Coulter method.
[0030] When the resin substrate 10 contains an AB agent, the content of the AB agent is preferably, for example, 0.05 to 0.5 parts by mass relative to 100 parts by mass of the resin constituting the resin substrate 10. When the content of the AB agent is equal to or more than the above lower limit, it is easy to improve the processing characteristics of the film that is the raw material of the resin substrate 10. When the content of the AB agent is equal to or less than the above upper limit, it is easy to suppress a decrease in the oxygen barrier property of the gas barrier film 1.
[0031] The black area ratio of one surface 12 of the resin substrate 10 is 0.15% or less, more preferably 0.12% or less, and even more preferably 0.10% or less. When the black area ratio is equal to or less than the above upper limit, the oxygen barrier property of the gas barrier film 1 is more likely to be improved. In addition, when the black area ratio is equal to or less than the above upper limit, the printability of the gas barrier film 1, particularly when using a polypropylene film or a polyethylene terephthalate resin film, is easily improved. The lower limit of the black area ratio is not particularly limited and is 0% or more.
[0032] Here, "improving printability" refers to suppressing ink loss (sometimes called dot loss) in highlight areas (printed areas with low dot area ratios) when gravure printing is performed on the oxygen barrier coating 20 of the gas barrier film. The black area ratio can be adjusted, for example, by the material, average particle size and content of the AB agent contained in the resin substrate 10, the properties of the resin forming one surface 12 of the resin substrate 10, the manufacturing conditions of the film, etc.
[0033] When the surface brightness of the resin substrate 10 is binarized and the black spots (black spots) are observed under an electron microscope, protrusions are present. The larger the black spots are, the higher the protrusions tend to be. 2 In locations where black dots (protrusions) of this size or larger are present, coating defects in the oxygen barrier coating and ink loss during printing are likely to occur. In other words, the smaller the black area ratio, the fewer protrusions that adversely affect the oxygen barrier property and printability on one side 12 of the resin substrate 10, and the more improved the oxygen barrier property of the gas barrier film 1 and the better the printability.
[0034] The black area ratio in this specification can be measured by the following measurement method. <Measurement method> An arbitrary region of 1281 μm square on one surface 12 of the resin substrate 10 is photographed with an optical microscope to obtain a photographed image of 1024×1024 pixels. An example of the photographed image is shown in FIG.
[0035] Fig. 2 is an image of one surface 12 of the resin substrate 10 photographed by an optical microscope. In Fig. 2, 100 denotes a flat portion, and 110 denotes a protrusion. Examples of the protrusion 110 include foreign matter, an AB agent, and residual resin. As shown in Fig. 2, the flat portion 100 appears gray, and the protrusion 110 appears black. The brightness of the flat portion 100 corresponds to the most frequent brightness value described later.
[0036] Next, the captured 1024 x 1024 pixel image is converted into a 256-level monochrome image using image analysis software. The brightness distribution in the converted monochrome image is plotted to create a histogram. An example of the histogram is shown in Figure 3.
[0037] In FIG. 3, the horizontal axis represents luminance converted into a monochrome image with 256 gradations. Luminance in a monochrome image is an integer between 0 and 255. The vertical axis represents the frequency of luminance. In FIG. 3, the minimum and maximum values of the distributed luminance are 26 and 255, respectively. The most frequent luminance value is the luminance value that is most frequently distributed in a monochrome image. P in FIG. 3 represents the most frequent luminance value. In FIG. 3, P=160.
[0038] Next, the brightness in the monochrome image is binarized by setting a threshold value obtained by subtracting 30 from the most frequent brightness value, and setting values below the threshold as black and values above the threshold as white. In the monochrome image of FIG. 3, the threshold value that marks the boundary between black and white is the most frequent brightness value subtracted 30 (P-30). In FIG. 3, the threshold is 130. That is, in FIG. 3, the binarization process is performed by setting brightness below 130 as "black" and brightness above 130 as "white."
[0039] From the viewpoint of improving the accuracy of the black area ratio value, it is preferable that the luminance histogram of the acquired image has a sharp shape. Here, a "sharp shape" can be determined, for example, by the width W of the histogram at half the height (H / 2) of the peak height H at the mode P of the histogram (hereinafter also referred to as "half-width"). For example, the half-width W is preferably 30 or less, more preferably 20 or less, and even more preferably 10 or less. When the half-width W is equal to or less than the above upper limit, the histogram has a sharp shape, and the accuracy of the black area ratio value can be improved. The lower limit of the half-width W is not particularly limited, but is substantially 2 or more.
[0040] From the binarized 1281 x 1281 μm (1024 x 1024 pixel) image, 2 The ratio of the total area of the black areas of the above size is the black area ratio. The black area ratio is the arithmetic average of the values obtained in any three areas.
[0041] As the optical microscope, the optical microscope "OLS-4000" manufactured by Olympus Corporation is preferable. As the image analysis software, "Scion ImageJ" manufactured by Scion Corporation is preferable. stomach.
[0042] The image acquisition conditions will be described. (Image acquisition conditions) The resin substrate 10 for which the black area ratio is to be calculated is attached to a slide glass using a black film double-sided tape (Teraoka Seisakusho, 7694) with the side (one side 12) on which the coating agent is applied facing up. Using an optical microscope (Olympus, OLS-4000) and a 10x objective lens (MPFLN10), images of a range of 1281 μm x 1281 μm are obtained from any three points of the resin substrate 10 on the slide glass as 1024 x 1024 pixel images. The amount of light when taking the image is arbitrary, but it is preferable to adjust the amount of light so that the most frequent value of the image brightness is in the range of 80 to 200 in 256 gradations.
[0043] The image analysis conditions are as follows. (Image analysis conditions) -Discard color information: 8bit. ·Binarization threshold: The most frequent luminance value minus 30. Scale setting: Set Scale Distance in pixel: 1024, Known distance: 1281, Unit of length: μm ·Area measurement:Analyze Particles Size:100-Infinity(μm 2 ), Check Include Holes and Summarize. Under the above image analysis conditions, the %Area value is calculated for each of the images taken from any three positions on the resin substrate 10, and the arithmetic mean value of these %Area values is defined as the black area ratio.
[0044] The black area ratio in this specification is calculated by observing the surface 12 of the resin substrate 10 in a plane. Therefore, compared to conventional surface roughness measurements, the surface condition can be observed in terms of a plane rather than a line.
[0045] Conventional surface roughness values vary depending on the measurement method and range. If the measurement area is small, the roughness may be underestimated because the few protrusions are not measured. Even when measuring roughness over a linear range of a certain length, such as the center line average roughness, if large protrusions are measured, the roughness will be overestimated, but if not, the roughness will still be underestimated.
[0046] By defining the surface condition of the resin substrate by the black area ratio as described in this specification, the surface condition of the resin substrate can be evaluated with reduced variation in the surface condition of the resin substrate, which makes it possible to suppress variation in the oxygen barrier property and to more easily improve the oxygen barrier property of the gas barrier film 1.
[0047] Controlling the black area ratio by binarising optical microscope images is suitable for controlling oxygen barrier properties and printability, as it has a wide measurement range and allows protrusions to be found in a simple manner.
[0048] The thickness of the resin substrate 10 is not particularly limited, and is appropriately selected according to the price and application, taking into consideration the suitability as a packaging material and the suitability for laminating other films. The thickness of the resin substrate 10 is preferably 3 μm to 200 μm, more preferably 5 μm to 120 μm, further preferably 6 μm to 100 μm, and particularly preferably 10 μm to 30 μm.
[0049] <Underlayer> The underlayer 30 is provided between the resin substrate 10 and the inorganic oxide layer 40 or the oxygen barrier film 20 .
[0050] The underlayer 30 is a layer containing an organic polymer as a main component, and is sometimes called a primer layer. By providing the underlayer 30, the film-forming properties and adhesive strength of the inorganic oxide layer 40 or the oxygen barrier coating 20 can be improved.
[0051] The content of the organic polymer in the underlayer 30 may be, for example, 70% by mass or more, or 80% by mass or more. Examples of the organic polymer include polyacrylic resin, polyester resin, polycarbonate resin, polyurethane resin, polyamide resin, polyolefin resin, polyimide resin, melamine resin, and phenol resin. Considering the hot water resistance of the adhesive strength between the resin substrate 10 and the inorganic oxide layer 40 or the oxygen barrier film 20, it is preferable that the underlayer 30 contains at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers. The underlayer 30 may also contain a silane coupling agent, an organic titanate, or a modified silicone oil.
[0052] More preferred examples of the organic polymer include an organic polymer having a urethane bond produced by the reaction of a polyol having two or more hydroxyl groups at the polymer terminal with an isocyanate compound, and / or an organic polymer containing a reaction product of a polyol having two or more hydroxyl groups at the polymer terminal with an organic silane compound such as a silane coupling agent or a hydrolyzate thereof.
[0053] Examples of polyols include at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol. The acrylic polyol may be obtained by polymerizing an acrylic acid derivative monomer, or may be obtained by copolymerizing an acrylic acid derivative monomer with another monomer. Examples of the acrylic acid derivative monomer include ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate. Examples of the monomer to be copolymerized with the acrylic acid derivative monomer include styrene.
[0054] The isocyanate compound has the effect of increasing the adhesion between the resin substrate 10 and the inorganic oxide layer 40 or the oxygen barrier film 20 by forming a urethane bond by reacting with the polyol. That is, the isocyanate compound functions as a crosslinking agent or a curing agent. Examples of the isocyanate compound include aromatic tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), aliphatic xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), and isophorone diisocyanate (IPDI) monomers, polymers thereof, and derivatives thereof. The above-mentioned isocyanate compounds may be used alone or in combination of two or more.
[0055] Examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane. The organic silane compound is The organic silane compound may contain one of the above-mentioned silane coupling agents and their hydrolysates alone, or two or more of them in combination.
[0056] The underlayer 30 can be formed by preparing a mixed solution by blending the above-mentioned components in an organic solvent in any ratio, and using the mixed solution prepared on one surface 12 of the resin substrate 10. The mixed solution may contain, for example, a curing accelerator such as a tertiary amine, an imidazole derivative, a metal salt compound of a carboxylic acid, a quaternary ammonium salt, or a quaternary phosphonium salt; an antioxidant such as a phenol-based, sulfur-based, or phosphite-based antioxidant; a leveling agent; a flow control agent; a catalyst; a crosslinking reaction accelerator; a filler, etc.
[0057] The mixed liquid can be coated on the resin substrate 10 by using a known printing method such as offset printing, gravure printing, or silk screen printing, or a known application method such as roll coating, knife edge coating, or gravure coating. After coating, the undercoat layer 30 can be formed by heating to, for example, 50 to 200° C. and drying and / or curing.
[0058] The thickness of the underlayer 30 is not particularly limited and may be, for example, 0.005 to 5 μm. The thickness may be adjusted depending on the application or the desired characteristics. The thickness of the underlayer 30 is preferably 0.01 to 1 μm, and more preferably 0.01 to 0.5 μm. If the thickness of the underlayer 30 is 0.01 μm or more, sufficient adhesive strength is obtained between the resin substrate 10 and the inorganic oxide layer 40 or the oxygen barrier film 20, and the oxygen barrier property is also good. If the thickness of the underlayer 30 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing costs can be suppressed.
[0059] <Inorganic oxide layer> Examples of the inorganic oxide layer 40 include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, tin oxide, zinc oxide, and indium oxide, and aluminum oxide or silicon oxide is particularly preferred because of its excellent productivity, heat resistance, and resistance to moist heat and oxygen barrier properties and water vapor barrier properties. The inorganic oxide layer 40 may contain one of these alone or two or more of them in combination.
[0060] The thickness of the inorganic oxide layer 40 is preferably 1 to 200 nm. If the thickness is 1 nm or more, excellent oxygen barrier properties and water vapor barrier properties can be obtained, and if the thickness is 200 nm or less, the manufacturing cost can be kept low, cracks due to external forces such as bending and pulling are unlikely to occur, and deterioration of the barrier properties can be suppressed.
[0061] The inorganic oxide layer 40 can be formed by a known film formation method such as vacuum deposition, sputtering, ion plating, or plasma chemical vapor deposition (CVD).
[0062] <Oxygen barrier coating> The oxygen barrier film 20 may be a known oxygen barrier film formed by a wet coating method. The oxygen barrier film 20 is obtained by forming a coating film made of a coating agent on the underlayer 30 or the inorganic oxide layer 40 by a wet coating method, and drying the coating film. The coating film is a wet film, and the film is a dry film.
[0063] The oxygen barrier film 20 is preferably a film containing at least one of a metal alkoxide and its hydrolysate or its reaction product, and a water-soluble polymer (organic-inorganic composite film), and more preferably a film further containing at least one of a silane coupling agent and its hydrolysate.
[0064] Examples of metal alkoxides and their hydrolysates contained in the organic-inorganic composite film include tetraethoxysilane [Si(OC 2 H 5 ) 4 ] and triisopropoxyaluminum [Al(OC 3 H 7 ) 3 and hydrolysates thereof. One of these may be contained alone, or two or more may be contained in combination.
[0065] The total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane is, for example, 40 to 70 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 50 mass%. From the same viewpoint, the upper limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 65 mass%.
[0066] The water-soluble polymer contained in the organic-inorganic composite film is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polysaccharides such as starch, methyl cellulose, and carboxymethyl cellulose, and acrylic polyol-based polymers. From the viewpoint of further improving the oxygen gas barrier property, the water-soluble polymer preferably contains a polyvinyl alcohol-based polymer. The number average molecular weight of the water-soluble polymer is, for example, 40,000 to 180,000.
[0067] A water-soluble polymer such as polyvinyl alcohol can be obtained by, for example, saponifying polyvinyl acetate (including partial saponification). This water-soluble polymer may have several tens of percent of acetate groups remaining, or may have only a few percent of acetate groups remaining.
[0068] The content of the water-soluble polymer in the organic-inorganic composite film is, for example, 15 to 50 mass%. The lower limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 20 mass% from the viewpoint of further reducing oxygen permeability. The upper limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 45 mass% from the viewpoint of further reducing oxygen permeability.
[0069] The silane coupling agent and its hydrolysate contained in the organic-inorganic composite film include silane coupling agents having organic functional groups. Such silane coupling agents and their hydrolysates include ethyltrimethoxysilane, vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and their hydrolysates. One of these may be contained alone, or two or more may be contained in combination.
[0070] At least one of the silane coupling agent and its hydrolysate is preferably used with an epoxy group as an organic functional group. Examples of the silane coupling agent with an epoxy group include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent with an epoxy group and its hydrolysate may have an organic functional group different from the epoxy group, such as a vinyl group, an amino group, a methacryl group or a ureyl group.
[0071] A silane coupling agent having an organic functional group and its hydrolysate can further improve the oxygen barrier property of the oxygen barrier coating 20 and the adhesion to the underlayer 30 or the inorganic oxide layer 40 through the interaction between the organic functional group and the hydroxyl group of the water-soluble polymer. In particular, an oxygen barrier coating 20 that is particularly excellent in oxygen barrier property and adhesion to the underlayer 30 or the inorganic oxide layer 40 can be formed through the interaction between the epoxy group of the silane coupling agent and its hydrolysate and the hydroxyl group of polyvinyl alcohol.
[0072] The total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film is, for example, 1 to 15 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 2 mass%. From the same viewpoint, the upper limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 12 mass%.
[0073] The organic-inorganic composite film may contain a crystalline inorganic layered compound having a layered structure. Examples of the inorganic layered compound include clay minerals such as kaolinite, smectite, and mica. These may be used alone or in combination of two or more. The particle size of the inorganic layered compound is, for example, 0.1 to 10 μm. The aspect ratio of the inorganic layered compound is, for example, 50 to 5000.
[0074] As the inorganic layered compound, a clay mineral of the smectite group is preferable because a water-soluble polymer can be inserted between the layers of the layered structure (intercalation) to form a film having excellent oxygen barrier properties and adhesive strength. Specific examples of the clay mineral of the smectite group include montmorillonite, hectorite, saponite, water-swellable synthetic mica, etc.
[0075] Another preferred example of the oxygen barrier film 20 is a film containing a polyvalent metal salt of carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) (polycarboxylic acid polyvalent metal salt film). In this case, the film may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent in which a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) are mixed and then heated and dried, or it may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent mainly composed of a polycarboxylic acid polymer (A) and drying to form a film A, applying a coating agent mainly composed of a polyvalent metal compound (B) on the film A, and then drying the coating to form a film B, and then allowing a crosslinking reaction between the A and B layers.
[0076] [Polycarboxylic acid polymer (A)] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in the molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having a carboxyl group in the molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.
[0077] Among the above, from the viewpoint of the gas barrier properties of the resulting gas barrier film 1, the component is preferably a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid, and particularly preferably a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid. In the polymer, the proportion of the structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (wherein the total of all structural units constituting the polymer is 100 mol%). The polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing structural units other than the above structural units, examples of the other structural units include structural units derived from ethylenically unsaturated monomers copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.
[0078] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the resulting gas barrier film cannot achieve sufficient water resistance, and the gas barrier property and transparency may deteriorate due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent when forming the oxygen barrier film 20 may increase, and the coatability may be impaired. The number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).
[0079] In the case where a coating agent mainly composed of a polycarboxylic acid polymer (A) is applied and dried to form a film A, and then a film B is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the film A can be further improved. As the basic compound, at least one basic compound selected from the group consisting of polyvalent metal compounds, monovalent metal compounds, and ammonia is preferable. As the polyvalent metal compound, the compounds exemplified in the description of the polyvalent metal compound (B) described later can be used. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.
[0080] Various additives can be added to the coating agent containing the polycarboxylic acid polymer (A) as the main component. These include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners and the like, within the range that does not impair the barrier performance.
[0081] The solvent used in the coating agent containing polycarboxylic acid polymer (A) as the main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, or mixtures thereof. The aqueous medium usually contains water or water as the main component. The content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran, cellosolves, carbitols, and nitriles such as acetonitrile.
[0082] [Polyvalent metal compounds (B)] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Zinc oxide is preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating.
[0083] Zinc oxide is an inorganic material capable of absorbing ultraviolet light. The average particle size of the zinc oxide particles is not particularly limited, but from the viewpoints of gas barrier properties, transparency, and coating suitability, the average particle size is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.
[0084] When a coating agent containing a polyvalent metal compound (B) as a main component is applied and dried to form a film, various additives may be contained in addition to zinc oxide particles as necessary within a range that does not impair the effects of the present disclosure. The additives may include a resin soluble or dispersible in a solvent used in the coating agent, a dispersant soluble or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent, a thickener, etc.
[0085] Among the above, the solvent used in the coating agent preferably contains a resin that is soluble or dispersible in the solvent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, and isocyanate resins.
[0086] It is also preferable to contain a dispersant that is soluble or dispersible in the solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. As the surfactant, various surfactants such as (poly)carboxylate, alkyl sulfate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkylsulfosuccinate, alkyldiphenylether disulfonate, alkylphosphate, aromatic phosphate, polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, alkylallyl sulfate, polyoxyethylene alkylphosphate, sorbitan alkyl ester, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyethylene glycol fatty acid ester, polyoxyethylene sorbitan alkyl ester, polyoxyethylene alkylallyl ether, polyoxyethylene derivative, polyoxyethylene sorbitol fatty acid ester, polyoxy fatty acid ester, and polyoxyethylene alkylamine can be mentioned. These surfactants may be used alone or in a mixture of two or more.
[0087] When an additive is contained in a coating agent mainly composed of a polyvalent metal compound (B), the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.
[0088] Examples of the solvent used in the coating agent containing polyvalent metal compound (B) as a main component include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coating property, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.
[0089] When a coating agent containing a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) is applied and dried to form a polycarboxylic acid polyvalent metal salt film, the polycarboxylic acid polymer (A) and the polyvalent metal compound (B) are mixed with a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary, and the mixture is applied and dried by a known coating method to form a polycarboxylic acid polyvalent metal salt film. Examples of the coating method include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metaling bar coating, chamber doctor combined coating, curtain coating, etc.
[0090] The thickness of the oxygen barrier film 20 is set according to the required oxygen barrier properties, and may be, for example, 0.05 to 5 μm. The thickness of the oxygen barrier film 20 is preferably 0.05 to 1 μm, more preferably 0.1 to 0.5 μm. If the thickness of the oxygen barrier film 20 is 0.05 μm or more, sufficient oxygen barrier properties are easily obtained. If the thickness of the oxygen barrier film 20 is 1 μm or less, it is easy to form a uniform coating surface, the drying load and manufacturing costs can be suppressed, and the usefulness of using the resin substrate 10 having a surface with a black area ratio of 0.15% or less, which is a feature of the present disclosure, is increased.
[0091] A gas barrier film having the above-mentioned organic-inorganic composite film or the above-mentioned polyvalent metal salt film of polycarboxylic acid as the oxygen barrier film 20 exhibits excellent oxygen barrier properties even when subjected to boiling treatment or retort sterilization treatment, and when laminated with a sealant film, has sufficient adhesion strength and sealing strength as a packaging material for boiling or retort treatment. Furthermore, it has advantages such as transparency not found in metal foils or metal vapor-deposited films, excellent bending resistance and stretching resistance, and no risk of generating harmful substances such as dioxins.
[0092] [Method of manufacturing gas barrier film] The gas barrier film 1 can be produced by forming an underlayer 30, an inorganic oxide layer 40, or both the underlayer 30 and the inorganic oxide layer 40 on one surface 12 of a resin substrate 10, and then forming an oxygen barrier coating 20 on the underlayer 30 or the inorganic oxide layer 40.
[0093] The method for producing the gas barrier film 1 of the present disclosure includes, for example, a selection step, a base layer forming step, an inorganic oxide layer forming step, and an oxygen barrier coating forming step.
[0094] The selection step may be, for example, a step of selecting a resin substrate raw sheet having a surface black area ratio of 0.15% or less as the resin substrate. The surface black area ratio of the resin substrate raw sheet is measured by a method similar to the method for measuring the black area ratio of one surface 12 of the resin substrate 10 described above.
[0095] The resin substrate 10 may be a commercially available product or may be produced by a known method.
[0096] An example of the underlayer formation process is a process in which a coating agent is applied to at least one surface 12 of the resin substrate 10 by a wet coating method to form a coating film, and the coating film is dried (to remove the solvent) to form the underlayer 30.
[0097] The coating agent can be applied by a known wet coating method, such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating.
[0098] The method for drying the coating film made of the coating agent can be a known drying method such as hot air drying, heat roll drying, infrared irradiation, etc. The drying temperature for the coating film is preferably, for example, 50 to 200° C. The drying time varies depending on the thickness of the coating film, the drying temperature, etc., but is preferably, for example, 1 second to 5 minutes.
[0099] The inorganic oxide layer forming process may be, for example, a process of forming an inorganic oxide layer 40 on one surface 12 of the resin substrate 10 or on the underlayer 30 by the above-mentioned vacuum deposition method, sputtering method, ion plating method, plasma chemical vapor deposition (CVD) method, or the like.
[0100] An example of the oxygen barrier film forming process is a process in which a coating agent is applied onto the underlayer 30 or the inorganic oxide layer 40 by a wet coating method to form a coating film, and the coating film is then dried (to remove the solvent) to form the oxygen barrier film 20.
[0101] The coating agent can be applied by a known wet coating method, such as roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating.
[0102] The method for drying the coating film made of the coating agent can be a known drying method such as hot air drying, heat roll drying, infrared irradiation, etc. The drying temperature for the coating film is preferably, for example, 50 to 200° C. The drying time varies depending on the thickness of the coating film, the drying temperature, etc., but is preferably, for example, 1 second to 5 minutes.
[0103] The oxygen barrier film 20 may be formed by a single coating and drying process, or may be formed by multiple coatings and drying processes using the same or different coating agents.
[0104] In the underlayer forming step, inorganic oxide layer forming step, and oxygen barrier film forming step, the underlayer 30, inorganic oxide layer 40, or oxygen barrier film 20 is formed on one surface 12 of the resin substrate 10. At this time, the black area ratio of the one surface 12 is 0.15% or less. Furthermore, the underlayer 30, inorganic oxide layer 40, or oxygen barrier film 20 may be formed on both surfaces of the resin substrate 10. In that case, the black area ratio of the other surface 14 of the resin substrate 10 is 0.15% or less.
[0105] When forming the undercoat layer 30, inorganic oxide layer 40, or oxygen barrier film 20 on both sides of the resin substrate raw material, it is preferable that the black area ratio on both sides of the resin substrate raw material is 0.15% or less, as this further enhances the oxygen barrier properties and provides good printability.
[0106] When the manufacturing method of the gas barrier film 1 of the present disclosure includes a selection step, a resin substrate having a surface black area ratio of 0.15% or less can be efficiently used. Therefore, by including the selection step, a gas barrier film 1 having improved oxygen barrier properties can be efficiently manufactured. In addition, by including the selection step, a gas barrier film 1 having good printability can be efficiently manufactured.
[0107] The gas barrier film 1 of the present disclosure may further include a printed layer, a protective layer, a light-shielding layer, an adhesive layer, a heat-sealable heat-fusible layer, and other functional layers, as necessary.
[0108] When the gas barrier film 1 of the present disclosure has a heat-sealable heat-sealable layer, this heat-sealable layer is disposed on at least one outermost layer of the gas barrier film 1. When the gas barrier film 1 has a heat-sealable layer, the gas barrier film 1 becomes one that can be sealed by heat sealing (for example, a package or a lid).
[0109] The heat-sealing layer can be formed, for example, by laminating a laminate obtained by forming the underlayer 30 of this embodiment, the inorganic oxide layer 40, and the oxygen barrier film 20 on one or both sides of a resin substrate, using a known adhesive such as a polyurethane-based, polyester-based, or polyether-based adhesive by a known dry lamination method, extrusion lamination method, or the like.
[0110] <Action and effect> The gas barrier film 1 of the present disclosure binarizes the brightness of a monochrome image and detects the brightness of the monochrome image at 100 μm 2 The total area ratio (black area ratio) of the black regions of the above size is calculated. On at least one surface of the resin substrate 10 having a black area ratio of 0.15% or less, an oxygen barrier film 20 is laminated via an underlayer 30, an inorganic oxide layer 40, or both the underlayer 30 and the inorganic oxide layer 40.
[0111] In the gas barrier film 1 of the present disclosure, the oxygen barrier coating 20 is formed on the surface of the resin substrate 10 having a black area ratio of 0.15% or less via the undercoat layer 30, the inorganic oxide layer 40, or both, so that film defects caused by large protrusions on the substrate surface are unlikely to occur, and the oxygen barrier properties are more likely to be improved. In addition, the printability of the gas barrier film 1 is more likely to be improved.
[0112] Therefore, by using the gas barrier film 1 of the present disclosure as a packaging material, the quality retention of the contents can be improved at low cost.
[0113] In addition, by using the gas barrier film 1 of the present disclosure as a packaging material, printing can be easily and beautifully applied.
[0114] (Embodiment 2) As described above, gas barrier films in which a coating is provided on the surface of a resin substrate by a wet coating method, a vapor deposition method, a sputtering method, or the like, sometimes have unstable oxygen barrier properties depending on the production lot. Specifically, the oxygen barrier properties of the gas barrier film are sometimes inferior to the inherent oxygen barrier properties, that is, the oxygen barrier properties expected from the material constituting the coating and the thickness of the coating. In particular, when the thickness of the coating is thin, such problems tend to occur easily. Therefore, it is necessary to deal with this by making the gas barrier layer thicker than necessary, which causes problems of poor productivity and excessive material costs.
[0115] Furthermore, polyolefin resin-based films are inexpensive and have high water vapor barrier properties as a resin substrate, and are therefore often used as packaging materials. However, they have a drawback in that they have poor adhesion to gas barrier coatings, and therefore when laminated with a heat-sealable resin film to form a gas barrier packaging material, the laminate strength is poor.
[0116] An object of the second embodiment is to provide a gas barrier film that exhibits excellent gas barrier properties by fully expressing its inherent oxygen barrier properties even when the thickness of the coating for imparting oxygen barrier properties is thin, and that has sufficient adhesive strength for use as a packaging material, and a method for producing the same.
[0117] In order to investigate the cause of the above problem, the present inventors conducted detailed observations of the surface and cross section of a gas barrier film with poor oxygen barrier properties using an optical microscope and an electron microscope. As a result of performing cross-sectional electron microscope observations using a focused ion / electron beam processing and observation device at the location where an antiblocking agent (hereinafter also referred to as "AB agent"), which is added to prevent blocking of the resin substrate, is present, it was confirmed that defects of several μm in width were generated in the film at the location where the AB agent protruded highly. (An example of a cross-sectional electron microscope image is shown in FIG. 8.) It is considered that these film defects became a path for gas permeation, and oxygen barrier properties were not fully expressed. On the surface of the resin substrate, there are protrusions of various sizes due to the AB agent. The protrusion height and protrusion density of the AB agent vary depending on the production lot of the resin substrate, and it is considered that when a gas barrier film (oxygen barrier film) is coated on the surface of the resin substrate, a film is not formed locally at the position of the large protrusions, defects are generated, and oxygen barrier properties are unstable.
[0118] Therefore, the present inventors have devised a method for accurately grasping, in a short period of time, the surface condition over a wide range of a resin substrate, which affects the oxygen barrier property of a gas barrier film, and have arrived at the present disclosure.
[0119] [1] A resin substrate and an oxygen barrier coating formed on a first surface side of the resin substrate, the resin substrate having at least one of an undercoat layer and an inorganic oxide layer between the resin substrate and the oxygen barrier coating, the resin substrate having two or more resin layers, the resin layer forming the first surface of the two or more resin layers being made of a polyolefin copolymer resin, and the first surface having protrusions with a Feret's diameter of 8 μm or more at a rate of 20 / mm 2 The gas barrier film is as follows: <Measurement method> A white LED line light source is used to irradiate an arbitrary 36.6 mm square area on the first surface of the resin substrate with light at a light source distance of 100 mm and an incidence angle of 83°. The transmitted light is captured at a measurement angle of 90° with a monochrome line camera to obtain a captured image. An analysis image of 3551 pixels x 5684 pixels (2.5 x 4.0 mm) is cut out from the captured image, and protrusions with a Feret's diameter of 8 μm or more in the analysis image are counted.
[0120] [2] The gas barrier film, wherein the resin substrate is a polyolefin resin.
[0121] [3] A gas barrier film, wherein the undercoat layer has a thickness of 0.01 to 1 μm.
[0122] [4] A gas barrier film, wherein the undercoat layer contains an organic polymer as a main component, and the organic polymer contains at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers.
[0123] [5] A gas barrier film, wherein the inorganic oxide layer has a thickness of 1 to 200 nm.
[0124] [6] The gas barrier film, wherein the inorganic oxide layer is aluminum oxide or silicon oxide.
[0125] [7] A gas barrier film, wherein the oxygen barrier coating has a thickness of 0.05 to 1 μm.
[0126] [8] The oxygen barrier film is formed from at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, and a reaction product of a metal alkoxide or a hydrolysate of a metal alkoxide. The gas barrier film is a coating containing a water-soluble polymer.
[0127] [9] A gas barrier film, wherein the oxygen barrier coating further comprises at least one of a silane coupling agent, a hydrolysate of a silane coupling agent, and a reaction product of a silane coupling agent or a hydrolysate of a silane coupling agent.
[0128]
[10] A gas barrier film, wherein the oxygen barrier coating contains a polyvalent metal salt of a carboxylic acid which is a reaction product between a carboxyl group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B).
[0129]
[11] A method for producing a gas barrier film according to any one of [1] to
[10] , wherein the number of protrusions on one side of a raw resin substrate is measured by the following measurement method, and the number of protrusions having a Feret's diameter of 8 μm or more is 20 / mm 2 A method for producing a gas barrier film, comprising the steps of: preparing a resin substrate from a raw resin substrate as described below; and applying a coating agent to at least a first surface side of the resin substrate to form an oxygen barrier film. <Measurement method> A white LED line light source is used to irradiate an arbitrary 36.6 mm square area on the first surface of the resin substrate with light at a light source distance of 100 mm and an incidence angle of 83°. The transmitted light is captured at a measurement angle of 90° with a monochrome line camera to obtain a captured image. An analysis image of 3551 pixels x 5684 pixels (2.5 x 4.0 mm) is cut out from the captured image, and protrusions with a Feret's diameter of 8 μm or more in the analysis image are counted.
[0130] The gas barrier film of the present disclosure will be described with reference to an embodiment. FIG. 4 is a schematic cross-sectional view of a gas barrier film 101 according to embodiment 2. The dimensional ratio in FIG. 4 is different from the actual one for the sake of convenience of explanation. The gas barrier film 101 has a resin substrate 120, an underlayer 140, an inorganic oxide layer 150, and an oxygen barrier coating 130. Either the underlayer 140 or the inorganic oxide layer 150 may be omitted. The underlayer 140 is laminated in contact with the first surface 21 of the resin substrate 120, and the inorganic oxide layer 150 is laminated on the opposite surface of the underlayer 140 that is in contact with the resin substrate 120. The inorganic oxide layer 150 is laminated in contact with the underlayer 140, and the oxygen barrier coating 130 is located in contact with the opposite surface of the inorganic oxide layer 150 that is in contact with the underlayer 140. When the underlayer 140 is not provided, the inorganic oxide layer 150 is laminated on the first surface 21 of the resin substrate 120. When the inorganic oxide layer 150 is not provided, the oxygen barrier film 130 is laminated on the underlayer 140.
[0131] <Resin substrate> The resin substrate 120 has two or more resin layers including a base layer 25. In this embodiment, the resin substrate 120 has a base layer 25 and a surface layer 23 located on one surface of the base layer 25. The surface layer 23 constitutes a first surface 21 of the resin substrate 120. The resin substrate 120 contains a resin, and each layer constituting the resin substrate 120, including the surface layer 23 and the base layer 25, also contains a resin.
[0132] The base layer 25 adjusts the mechanical properties, chemical properties, thermal properties, optical properties, etc. of the resin substrate 120. Mechanical properties include rigidity, elongation, stiffness, tear strength, impact strength, puncture strength, pinhole resistance, etc. Chemical properties include water vapor barrier properties, gas barrier properties, aroma retention, chemical resistance, oil resistance, etc. Thermal properties include melting point, glass transition point, heat resistance, cold resistance, thermal shrinkage rate, etc. Optical properties include transparency, gloss, etc.
[0133] As the resin used as the raw material of the base layer 25, polyolefin resins are preferred from the viewpoints of availability and water vapor barrier properties. Examples of polyolefin resins include polyethylene, polypropylene, polybutene, and the like. Polypropylene may be any of homopolymers, random copolymers, and block copolymers. A homopolymer is a polypropylene consisting of only propylene alone. A random copolymer is a polypropylene in which the main monomer propylene and a different type of comonomer are randomly copolymerized to form a homogeneous phase. A block copolymer is a polypropylene in which the main monomer propylene and the above-mentioned comonomer are copolymerized in blocks or polymerized in a rubber-like form to form a heterogeneous phase. Any one of these polyolefin resins may be used alone, or two or more may be blended together.
[0134] The base layer 25 may contain an additive. The additive may be appropriately selected from various known additives. Examples of the additive include fillers, antiblocking agents (AB agents), heat stabilizers, weather stabilizers, UV absorbers, lubricants, slip agents, nucleating agents, antistatic agents, antifogging agents, pigments, and dyes. Any one of these additives may be used alone, or two or more may be used in combination. The content of the additive in the base layer 25 may be appropriately adjusted within a range that does not impede the effects of the present disclosure.
[0135] The base layer 25 may have a single-layer structure or a multi-layer structure. The thickness of the base layer 25 may be, for example, 3 to 200 μm, or 6 to 30 μm.
[0136] The surface layer 23 is composed of a polyolefin-based copolymer resin. Examples of polyolefin-based copolymer resins include ethylene-propylene copolymers, ethylene-1-butene copolymers, propylene-1-butene copolymers, propylene-pentene copolymers, ethylene-propylene-1-butene copolymers, ethylene-acrylic acid copolymers, ionomers in which ethylene-acrylic acid copolymers are crosslinked with metal ions, and propylene-acrylic acid copolymers, and the like, each of which may be a random copolymer or a block copolymer. Any one of these resins may be used alone, or two or more may be blended together. By making the surface layer 23 from a polyolefin-based copolymer resin, the adhesion to any one of the undercoat layer 140, the inorganic oxide layer 150, and the oxygen barrier film 130 laminated on the resin substrate 120 is improved.
[0137] The surface layer 23 may contain an additive. The additive may be appropriately selected from various known additives. Examples of the additive include an antiblocking agent (AB agent), a heat stabilizer, a weather stabilizer, an ultraviolet absorber, a lubricant, a slip agent, a nucleating agent, an antistatic agent, an antifogging agent, a pigment, and a dye. Any one of these additives may be used alone, or two or more may be used in combination. The content of the additive in the surface layer 23 may be appropriately adjusted within a range that does not impede the effects of the present disclosure.
[0138] When the surface layer 23 contains an AB agent, protrusions resulting from the AB agent are formed on the first surface 21 of the resin substrate 120. These protrusions prevent adhesion between films, improving the processability of the film roll when it is wound, unwound, and transported. In particular, the average particle size of the AB agent and the amount of addition affect the size and number of protrusions on the first surface 21, so it is preferable to use a protrusion density of 20 particles / mm2 or more with a Feret's diameter of 8 μm or more as measured by the measurement method described below. 2 It is desirable to adjust it as follows:
[0139] The AB agent is a solid particle, and examples thereof include organic particles and inorganic particles. Examples of the organic particles include polymethyl methacrylate particles, polystyrene particles, and polyamide particles. These organic particles are obtained, for example, by emulsion polymerization or suspension polymerization. Examples of the inorganic particles include silica particles, zeolite, talc, kaolinite, and feldspar. These AB agents may be used alone or in combination of two or more. As the AB agent, polymethyl methacrylate particles are preferred for the organic system, and silica particles are preferred for the inorganic system.
[0140] The average particle size of the AB agent is preferably 0.1 μm or more and 5 μm or less. From the viewpoint of achieving both anti-blocking performance and gas barrier performance of the gas barrier film 101, the average particle size of the AB agent is particularly preferably 1 μm or more and 4 μm or less. The average particle size of the AB agent is measured by the Coulter method.
[0141] The amount of the AB agent added is preferably, for example, 0.05 to 0.4 mass % relative to the total mass of the surface layer 23. The amount of the AB agent added in the surface layer 23 is specifically calculated by the following formula. Amount of AB agent added [mass%] = {(i) / 100} × {(ii) / 100} × 100 In the formula, (i) indicates the concentration (mass %) of the AB agent in masterbatch resin chips which are added to a resin, stirred, fed into an extruder and kneaded, and formed into pellets by melt extrusion. (ii) indicates the concentration (mass %) of the masterbatch resin chips containing the AB agent relative to the total mass of the resin pellets which constitute the surface layer 23 when the masterbatch resin chips containing the AB agent are blended with a resin which does not contain the AB agent. When the AB agent is added to the base layer 25, the amount of the AB agent added is also preferably 0.05 to 0.4 mass % relative to the total mass of the base layer 25, and the amount of the AB agent added can be calculated by the above formula.
[0142] The thickness of the surface layer 23 may be, for example, 0.1 to 10 μm, or may be 0.5 to 5.0 μm.
[0143] The resin substrate 120 is preferably a coextruded film including at least a surface layer 23 and a base layer 25. The resin substrate 120 may be a stretched film or an unstretched film.
[0144] The resin substrate 120 preferably has a biaxially oriented polypropylene film. Since biaxially oriented polypropylene films are particularly excellent in water vapor barrier performance, the gas barrier film 101 has improved water vapor barrier performance by having the biaxially oriented polypropylene film. The biaxially oriented polypropylene film may be at least one of homopolymers, random copolymers, block copolymers, etc., processed into a film shape. The biaxially oriented polypropylene film is preferably a coextruded film.
[0145] The base layer 25 may be made of a biaxially oriented polypropylene film, or may be a laminate of a biaxially oriented polypropylene film and another resin film. Examples of the other resin film include polyester films such as polyethylene terephthalate and polyethylene naphthalate, polyolefin resin films such as polyethylene, polystyrene films, polyamide films such as nylon, polycarbonate films, polyacrylonitrile films, and engineering plastic films such as polyimide films.
[0146] The thickness of the resin substrate 120 is not particularly limited, and is appropriately selected according to the price and application, taking into consideration suitability as a packaging material and suitability for laminating other films. The thickness of the resin substrate 120 is preferably 3 μm to 200 μm, more preferably 5 μm to 120 μm, and even more preferably 6 μm to 30 μm, from a practical standpoint.
[0147] The first surface 21 of the resin substrate 120 may be subjected to at least one treatment selected from the group consisting of a chemical treatment, a solvent treatment, a corona treatment, a plasma treatment, and an ozone treatment.
[0148] When protrusions are formed by the AB agent on the first surface 21 of the resin substrate 120, blocking of the film can be prevented, but on the other hand, in large convex portions, film defects that become paths for gas permeation are likely to occur in the undercoat layer 140, inorganic oxide layer 150, and oxygen barrier coating 130 formed thereon, and there is a risk of a decrease in the oxygen barrier properties of the gas barrier film 101. However, the first surface 21 of the resin substrate 120 of the gas barrier film 101 of the present disclosure has 20 protrusions / mm2 with a Feret's diameter of 8 μm or more as measured by the measurement method described below. 2 The first surface 21 of the resin substrate 120 has a protrusion density of 17 / mm2 or less with a Feret's diameter of 8 μm or more, and film defects are unlikely to occur. 2 It is more preferable that the number of protrusions per mm is 15 or less, and that the number of protrusions per mm is 8 μm or more. 2 It is more preferable that the number of protrusions having a Feret diameter of 8 μm or more is 0 / mm 2Many of the protrusions having a Feret's diameter of 8 μm or more have a height from the flat portion of the first surface 21 to the top of the protrusion that exceeds 1 μm, and are prone to causing film defects in the oxygen barrier coating. 2 If it is equal to or less than this, film defects are unlikely to occur in the underlayer 140, the inorganic oxide layer 150, and the oxygen barrier coating 130, which makes it easier to improve the oxygen barrier properties of the gas barrier film 101. The protrusions formed on the first surface 21 of the resin substrate 120 may be derived from the AB agent or may be due to other factors, and are not particularly limited. In this specification, the number of protrusions on the first surface 21 of the resin substrate 120 is a value measured by the following measurement method.
[0149] <Measurement method> An arbitrary 36.6 mm square area of the resin substrate 120 is irradiated with light from the second surface 22 side, which is the surface opposite to the first surface 21 of the resin substrate 120, at a light source distance of 100 mm and an incident angle of 83° using a white LED line light source. The transmitted light at a measurement angle of 90° is photographed with a monochrome line camera to obtain a photographed image. An analysis image of 3551 pixels x 5684 pixels (2.5 x 4.0 mm) is cut out from the photographed image. Protrusions with a Feret's diameter of 8 μm or more are extracted from the cut-out analysis image using image analysis software, and the number of protrusions is counted, and the measurement is performed using a 36.6 mm square. 2 This is calculated as the number of protrusions with a Feret diameter of 8 μm or more per square meter.
[0150] A method for measuring the number of protrusions on the first surface 21 of the resin base material 120 will be described below with reference to the drawings. First, the measuring device will be described.
[0151] (Measuring Equipment) As shown in FIG. 5, a measuring device 15 for measuring the number of protrusions on a first surface 21 of a resin substrate 120 includes a sample holder 2, a light source 4, and a monochrome line camera 7. The sample holder 2 is installed on a transport device 16 and can move horizontally. A punching hole 3 is formed in the center of the sample holder 2. The light source 4 is located below the sample holder 2 and is installed at a light source distance of 100 mm, and a light source control device 6 is connected to the light source control device 6. The monochrome line camera 7 is located above the sample holder 2, and a macro lens 8 is attached to the monochrome line camera 7. An image processing device 9 is connected to the image processing device 9. A transport control unit 17 is connected to the transport device 16.
[0152] There are no particular limitations on the sample holder 2 as long as it is flat and horizontal, and any known holder may be used. As the light source 4, a white LED line light source that emits visible light is preferable.
[0153] It is preferable to use a monochrome line camera 7 with 16384 pixels and a sensor size of 3.52 μm per pixel. The monochrome line camera 7 is preferably controlled by the image processing device 9 via a standard interface such as Camera Link or USB. The image processing device 9 is composed of, for example, a personal computer equipped with a frame grabber or the like that connects to the monochrome line camera 7, and image processing software that controls the frame grabber. Personal computers equipped with a frame grabber or the like and image processing software that controls the frame grabber are widely distributed or commercially available, and these can be used as the image processing device 9. An example of the image processing software is public domain software "ImageJ" developed by the National Institutes of Health (NIH).
[0154] It is preferable to use a one-axis stage driven by a stepping motor as the transport device 16. The transport device 16 is controlled by a transport control unit 17 in terms of transport speed, transport start, transport stop, and the like.
[0155] (Sample preparation) Next, a method for measuring the number of protrusions on the first surface of the resin substrate 120 will be described. As shown in Fig. 5, first, the first surface 21 of the resin substrate 120 is faced toward the monochrome line camera 7, and the resin substrate 120 is fixed to the sample holder 2 so that no height difference occurs within the surface. When fixing the resin substrate 120, it is preferable to fix the end of the resin substrate 120 using OPP tape, masking tape, or the like. The resin substrate 120 is fixed to the sample holder 2 so that the image measurement position 18 of the resin substrate 120 is aligned with the punching hole 3.
[0156] (Acquisition of photographed images) Next, white LED line light is incident from the light source 4. The light amount of the light source 4 can be adjusted by the light source control device 6. It is preferable to adjust the light amount of the incident light L1 by using the light source control device 6 so that the light amount at the image measurement position 18 is 442 lux. The incident light L1 from the light source 4 is shifted obliquely from the vertical direction by 7 degrees with the incident angle 13 to the first surface 21 being 83 degrees, and the monochrome line camera 7 is installed at a position where the measurement angle 19 to the first surface 21 is 90 degrees, and the transmitted light L2 transmitted through the image measurement position 18 is photographed by the monochrome line camera 7 through the macro lens 8. At this time, the magnification of the macro lens 8 is 5 times, the F value is 2.8, and the resolution is 0.704 μm. The measurement range of the monochrome line camera 7 at the image measurement position 18 is an area of 36.6 mm square, and the effective illumination range of the light source 4 is an area of 36.6 mm square or more.
[0157] The measurement range of the transmitted light L2 is a 36.6 mm square area of the first surface 21. The conveying device 16 is moved so that the measurement range is the above-mentioned area. When the conveying device 16 is a stepping motor or the like, a pulse signal indicating the conveying speed is input to the image processing device 9. The conveying speed at which the conveying device 16 is moved is preferably set to be equal to the product of the spatial resolution and the capture frequency. The spatial resolution is determined by the sensor size (3.52 μm) of the monochrome line camera 7 and the magnification (5 times) of the macro lens 8. The capture frequency is the capture frequency of one line of the monochrome line camera 7. The conveying speed is set to be equal to the product of the spatial resolution and the capture frequency, and the resin substrate 120 is conveyed continuously at the image measurement position 18 of the monochrome line camera 7. At the image measurement position 18, the monochrome line camera 7 measures and captures an image of the first surface 21 of the resin substrate 120.
[0158] The exposure time of the monochrome line camera 7 is set to 80 μs. The period of the capture frequency is set to be longer than the exposure time. The resin substrate 120 is transported, and an image of 5684 pixels or more is captured in the transport direction of the resin substrate 120.
[0159] (Image analysis) From the captured image, the central 3551 pixels corresponding to the sensor arrangement direction of the monochrome line camera 7 (the direction perpendicular to the conveying direction of the resin substrate 120) and 5684 pixels in the conveying direction are cut out to create an image for analysis. It is also possible to cut out more than 5684 pixels in the conveying direction to widen the measurement range. The cut-out image for analysis is analyzed using image analysis software.
[0160] FIG. 6 shows the principle by which minute protrusions and depressions on the surface of the resin substrate 120 can be detected in this measurement system. When the incident angle θ2 is made smaller than the measurement angle θ1 with a line camera, the protrusions are visualized three-dimensionally with the upper side of the image brighter and the lower side darker. In the depressions, the top and bottom are reversed. This is presumably due to refraction similar to that of a spherical lens. Using this tendency, bright particles and dark particles are selected and binarized from the analysis image according to their brightness, size, and roundness, respectively, and particles that are bright on the top and dark on the bottom are extracted as protrusions, and the Feret diameter data of the extracted particles is obtained. FIG. 7 shows a photographed image of the first surface 21 of the resin substrate 120 of the embodiment and an analysis image in which the protrusions are extracted using the above algorithm. From the Feret diameter data extracted in this way, the number of particles with a Feret diameter of 8 μm or more in the analysis image is counted, and the Feret diameter data is calculated in mm. 2 The number of protrusions was calculated as the number per area.
[0161] <Underlayer> The underlayer 140 is provided between the resin substrate 120 and the inorganic oxide layer 150 or the oxygen barrier film 130. The underlayer 140 is a layer containing an organic polymer as a main component, and is sometimes called a primer layer. By providing the underlayer 140, the film-forming properties and adhesive strength of the inorganic oxide layer 150 or the oxygen barrier film 130 can be improved.
[0162] The content of the organic polymer in the underlayer 140 may be, for example, 70% by mass or more, or 80% by mass or more. Examples of the organic polymer include polyacrylic resin, polyester resin, polycarbonate resin, polyurethane resin, polyamide resin, polyolefin resin, polyimide resin, melamine resin, and phenol resin. Considering the hot water resistance of the adhesive strength between the resin substrate 120 and the inorganic oxide layer 150 or the oxygen barrier film 130, it is preferable that the underlayer 140 contains at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, or a reaction product of these organic polymers. The underlayer 140 may also contain a silane coupling agent, an organic titanate, or a modified silicone oil.
[0163] More preferred examples of the organic polymer include an organic polymer having a urethane bond produced by the reaction of a polyol having two or more hydroxyl groups at the polymer terminal with an isocyanate compound, and / or an organic polymer containing a reaction product of a polyol having two or more hydroxyl groups at the polymer terminal with an organic silane compound such as a silane coupling agent or a hydrolyzate thereof.
[0164] Examples of polyols include at least one selected from acrylic polyol, polyvinyl acetal, polystyrene polyol, and polyurethane polyol. The acrylic polyol may be obtained by polymerizing an acrylic acid derivative monomer, or may be obtained by copolymerizing an acrylic acid derivative monomer with another monomer. Examples of the acrylic acid derivative monomer include ethyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and hydroxybutyl methacrylate. Examples of the monomer to be copolymerized with the acrylic acid derivative monomer include styrene.
[0165] The isocyanate compound has the effect of increasing the adhesion between the resin substrate 120 and the inorganic oxide layer 150 or the oxygen barrier film 130 by forming a urethane bond by reacting with the polyol. That is, the isocyanate compound functions as a crosslinking agent or a curing agent. Examples of the isocyanate compound include aromatic tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), aliphatic xylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), and isophorone diisocyanate (IPDI) monomers, polymers thereof, and derivatives thereof. The above-mentioned isocyanate compounds may be used alone or in combination of two or more.
[0166] Examples of silane coupling agents include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane. The organic silane compound may be a hydrolyzate of these silane coupling agents. The organic silane compound may contain one of the above-mentioned silane coupling agents and their hydrolyzates alone, or two or more of them in combination.
[0167] The underlayer 140 can be formed by preparing a mixed solution by mixing the above-mentioned components in an organic solvent in any ratio, and using the mixed solution prepared on the first surface 21 of the resin substrate 120. The mixed solution may contain, for example, a curing accelerator such as a tertiary amine, an imidazole derivative, a metal salt compound of a carboxylic acid, a quaternary ammonium salt, or a quaternary phosphonium salt; an antioxidant such as a phenol-based, sulfur-based, or phosphite-based antioxidant; a leveling agent; a flow regulator; a catalyst; a crosslinking reaction accelerator; a filler, and the like.
[0168] The mixed liquid can be coated on the resin substrate 120 by using a known printing method such as offset printing, gravure printing, or silk screen printing, or a known application method such as roll coating, knife edge coating, or gravure coating. After coating, the mixture can be heated to, for example, 50 to 200° C., and dried and / or cured to form the underlayer 140.
[0169] The thickness of the underlayer 140 is not particularly limited and may be, for example, 0.005 to 5 μm. The thickness may be adjusted depending on the application or the desired characteristics. The thickness of the underlayer 140 is preferably 0.01 to 1 μm, more preferably 0.01 to 0.5 μm. If the thickness of the underlayer 140 is 0.01 μm or more, sufficient adhesive strength between the resin substrate 120 and the inorganic oxide layer 150 or the oxygen barrier film 130 is obtained, and the oxygen barrier property is also good. If the thickness of the underlayer 140 is 1 μm or less, it is easy to form a uniform coating surface, and the drying load and manufacturing costs can be suppressed.
[0170] <Inorganic oxide layer> Examples of the inorganic oxide layer 150 include aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, tin oxide, zinc oxide, and indium oxide. In particular, aluminum oxide or silicon oxide is preferred because it has excellent productivity and excellent oxygen barrier properties and water vapor barrier properties in heat resistance and wet heat resistance. The inorganic oxide layer 150 may contain one of these alone or two or more in combination. The thickness of the inorganic oxide layer 150 is preferably 1 to 200 nm. If the thickness is 1 nm or more, excellent oxygen barrier properties and water vapor barrier properties are obtained, and if the thickness is 200 nm or less, the manufacturing cost can be kept low, cracks due to external forces such as bending and pulling are unlikely to occur, and deterioration of the barrier properties can be suppressed. The inorganic oxide layer 150 can be formed by a known film formation method such as a vacuum deposition method, a sputtering method, an ion plating method, or a plasma vapor phase growth method (CVD).
[0171] <Oxygen barrier coating> The oxygen barrier film 130 may be a known oxygen barrier film formed by a wet coating method. The oxygen barrier film 130 is obtained by forming a coating film made of a coating agent on the underlayer 140 or the inorganic oxide layer 150 by a wet coating method, and drying the coating film. The coating film is a wet film, and the film is a dry film.
[0172] The oxygen barrier film 130 is preferably a film (organic-inorganic composite film) containing at least one of a metal alkoxide and its hydrolysate or its reaction product and a water-soluble polymer, and more preferably a film further containing at least one of a silane coupling agent and its hydrolysate.
[0173] Examples of metal alkoxides and their hydrolysates contained in the organic-inorganic composite film include tetraethoxysilane [Si(OC 2 H 5 ) 4 ] and triisopropoxyaluminum [Al(OC3 H 7 ) 3 ] etc. general formula M(OR) n and hydrolysates thereof. One of these may be contained alone, or two or more of them may be contained in combination.
[0174] The total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane is, for example, 40 to 70 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 50 mass%. From the same viewpoint, the upper limit of the total content of at least one of the metal alkoxide and its hydrolysate and / or its reaction product in the organic-inorganic composite membrane may be 65 mass%.
[0175] The water-soluble polymer contained in the organic-inorganic composite film is not particularly limited, and examples thereof include polyvinyl alcohol-based polymers, polysaccharides such as starch, methyl cellulose, and carboxymethyl cellulose, and acrylic polyol-based polymers. From the viewpoint of further improving the oxygen gas barrier property, the water-soluble polymer preferably contains a polyvinyl alcohol-based polymer. The number average molecular weight of the water-soluble polymer is, for example, 40,000 to 180,000.
[0176] A water-soluble polymer such as polyvinyl alcohol can be obtained by, for example, saponifying polyvinyl acetate (including partial saponification). This water-soluble polymer may have several tens of percent of acetate groups remaining, or may have only a few percent of acetate groups remaining.
[0177] The content of the water-soluble polymer in the organic-inorganic composite film is, for example, 15 to 50 mass%. The lower limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 20 mass% from the viewpoint of further reducing oxygen permeability. The upper limit of the content of the water-soluble polymer in the organic-inorganic composite film may be 45 mass% from the viewpoint of further reducing oxygen permeability.
[0178] Silane coupling agents and their hydrolysates contained in the organic-inorganic composite film include silane coupling agents having an organic functional group. Examples of such silane coupling agents and their hydrolysates include ethyltrimethoxysilane, vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and their hydrolysates. One of these may be contained alone, or two or more may be contained in combination. .
[0179] At least one of the silane coupling agent and its hydrolysate is preferably used with an epoxy group as an organic functional group. Examples of the silane coupling agent with an epoxy group include γ-glycidoxypropyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane. The silane coupling agent with an epoxy group and its hydrolysate may have an organic functional group different from the epoxy group, such as a vinyl group, an amino group, a methacryl group or a ureyl group.
[0180] A silane coupling agent having an organic functional group and its hydrolysate can further improve the oxygen barrier property of the oxygen barrier coating 130 and the adhesion to the underlayer 140 or the inorganic oxide layer 150 through the interaction between the organic functional group and the hydroxyl group of the water-soluble polymer. In particular, an oxygen barrier coating 130 that is particularly excellent in oxygen barrier property and adhesion to the underlayer 140 or the inorganic oxide layer 150 can be formed through the interaction between the epoxy group of the silane coupling agent and its hydrolysate and the hydroxyl group of polyvinyl alcohol.
[0181] The total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film is, for example, 1 to 15 mass%. From the viewpoint of further reducing oxygen permeability, the lower limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 2 mass%. From the same viewpoint, the upper limit of the total content of at least one of the silane coupling agent and its hydrolysate and / or its reaction product in the organic-inorganic composite film may be 12 mass%.
[0182] The organic-inorganic composite film may contain a crystalline inorganic layered compound having a layered structure. Examples of the inorganic layered compound include clay minerals such as kaolinite, smectite, and mica. These may be used alone or in combination of two or more. The particle size of the inorganic layered compound is, for example, 0.1 to 10 μm. The aspect ratio of the inorganic layered compound is, for example, 50 to 5000.
[0183] As the inorganic layered compound, a clay mineral of the smectite group is preferable because a water-soluble polymer can be inserted between the layers of the layered structure (intercalation) to form a film having excellent oxygen barrier properties and adhesive strength. Specific examples of the clay mineral of the smectite group include montmorillonite, hectorite, saponite, water-swellable synthetic mica, etc.
[0184] Another preferred example of the oxygen barrier film 130 is a film containing a polyvalent metal salt of carboxylic acid, which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) (polycarboxylic acid polyvalent metal salt film). In this case, the film may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent containing a mixture of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) and drying by heating, or may be a polycarboxylic acid polyvalent metal salt film formed by applying a coating agent containing a polycarboxylic acid polymer (A) as a main component and drying to form a film A, applying a coating agent containing a polyvalent metal compound (B) as a main component thereon, drying to form a film B, and allowing a crosslinking reaction between the A / B layers.
[0185] [Polycarboxylic acid polymer (A)] A polycarboxylic acid polymer is a polymer having two or more carboxy groups in the molecule. Examples of polycarboxylic acid polymers include (co)polymers of ethylenically unsaturated carboxylic acids; copolymers of ethylenically unsaturated carboxylic acids and other ethylenically unsaturated monomers; and acidic polysaccharides having a carboxyl group in the molecule, such as alginic acid, carboxymethylcellulose, and pectin. Examples of ethylenically unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and crotonic acid. Examples of ethylenically unsaturated monomers copolymerizable with ethylenically unsaturated carboxylic acids include saturated carboxylic acid vinyl esters such as ethylene, propylene, and vinyl acetate, alkyl acrylates, alkyl methacrylates, alkyl itaconates, vinyl chloride, vinylidene chloride, styrene, acrylamide, and acrylonitrile. These polycarboxylic acid polymers may be used alone or in combination of two or more.
[0186] Among the above, from the viewpoint of the gas barrier properties of the resulting gas barrier film, the component is preferably a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, itaconic acid, fumaric acid, and crotonic acid, and particularly preferably a polymer containing a structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid. In the polymer, the proportion of the structural unit derived from at least one polymerizable monomer selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, and itaconic acid is preferably 80 mol% or more, more preferably 90 mol% or more (wherein the total of all structural units constituting the polymer is 100 mol%). The polymer may be a homopolymer or a copolymer. When the polymer is a copolymer containing structural units other than the above structural units, the other structural units may be, for example, a structural unit derived from an ethylenically unsaturated monomer copolymerizable with the above-mentioned ethylenically unsaturated carboxylic acid.
[0187] The number average molecular weight of the polycarboxylic acid polymer is preferably within the range of 2,000 to 10,000,000, and more preferably 5,000 to 1,000,000. If the number average molecular weight is less than 2,000, the resulting gas barrier film cannot achieve sufficient water resistance, and the gas barrier property and transparency may deteriorate due to moisture, or whitening may occur. On the other hand, if the number average molecular weight exceeds 10,000,000, the viscosity of the coating agent when forming the oxygen barrier film 130 may increase, and the coatability may be impaired. The number average molecular weight is a polystyrene-equivalent number average molecular weight determined by gel permeation chromatography (GPC).
[0188] In the case where a coating agent mainly composed of a polycarboxylic acid polymer (A) is applied and dried to form an A film, and then the B film is formed, a part of the carboxyl groups of the polycarboxylic acid polymer may be neutralized in advance with a basic compound. By neutralizing a part of the carboxyl groups of the polycarboxylic acid polymer in advance, the water resistance and heat resistance of the A film can be further improved. As the basic compound, at least one basic compound selected from the group consisting of polyvalent metal compounds, monovalent metal compounds, and ammonia is preferable. As the polyvalent metal compound, the compounds exemplified in the description of the polyvalent metal compound (B) described later can be used. As the monovalent metal compound, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned.
[0189] Various additives can be added to the coating agent containing the polycarboxylic acid polymer (A) as the main component. Examples of the additives include crosslinking agents, curing agents, leveling agents, defoamers, antiblocking agents, antistatic agents, dispersants, surfactants, softeners, stabilizers, film-forming agents, thickeners, and the like, provided that the additives do not impair the barrier performance.
[0190] The solvent used in the coating agent containing polycarboxylic acid polymer (A) as the main component is preferably an aqueous medium. Examples of the aqueous medium include water, water-soluble or hydrophilic organic solvents, or mixtures thereof. The aqueous medium usually contains water or water as the main component. The content of water in the aqueous medium is preferably 70% by mass or more, more preferably 80% by mass or more. Examples of the water-soluble or hydrophilic organic solvent include alcohols such as methanol, ethanol, and isopropanol, ketones such as acetone and methyl ethyl ketone, ethers such as tetrahydrofuran, cellosolves, carbitols, and nitriles such as acetonitrile.
[0191] [Polyvalent metal compounds (B)] The polyvalent metal compound is not particularly limited as long as it is a compound that reacts with the carboxyl group of the polycarboxylic acid polymer to form a polyvalent metal salt of polycarboxylic acid, and examples thereof include zinc oxide particles, magnesium oxide particles, magnesium methoxide, copper oxide, calcium carbonate, etc. These may be used alone or in combination. Zinc oxide is preferred from the viewpoint of the oxygen barrier properties of the oxygen barrier coating.
[0192] Zinc oxide is an inorganic material capable of absorbing ultraviolet light. The average particle size of the zinc oxide particles is not particularly limited, but from the viewpoints of gas barrier properties, transparency, and coating suitability, the average particle size is preferably 5 μm or less, more preferably 1 μm or less, and particularly preferably 0.1 μm or less.
[0193] When a coating agent mainly composed of a polyvalent metal compound (B) is applied and dried to form a B film, various additives may be contained in addition to zinc oxide particles as necessary within a range that does not impair the effects of the present disclosure. The additives may include a resin soluble or dispersible in a solvent used in the coating agent, a dispersant soluble or dispersible in the solvent, a surfactant, a softener, a stabilizer, a film-forming agent, a thickener, etc.
[0194] Among the above, it is preferable to contain a resin that is soluble or dispersible in the solvent used in the coating agent. This improves the coatability and film-forming properties of the coating agent. Examples of such resins include alkyd resins, melamine resins, acrylic resins, urethane resins, polyester resins, phenolic resins, amino resins, fluorine resins, epoxy resins, and isocyanate resins.
[0195] It is also preferable to contain a dispersant that is soluble or dispersible in the solvent used in the coating agent. This improves the dispersibility of the polyvalent metal compound. As the dispersant, an anionic surfactant or a nonionic surfactant can be used. As the surfactant, various surfactants such as (poly)carboxylate, alkyl sulfate, alkylbenzene sulfonate, alkylnaphthalene sulfonate, alkylsulfosuccinate, alkyldiphenylether disulfonate, alkylphosphate, aromatic phosphate, polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, alkylallyl sulfate, polyoxyethylene alkylphosphate, sorbitan alkyl ester, glycerin fatty acid ester, sorbitan fatty acid ester, sucrose fatty acid ester, polyethylene glycol fatty acid ester, polyoxyethylene sorbitan alkyl ester, polyoxyethylene alkylallyl ether, polyoxyethylene derivative, polyoxyethylene sorbitol fatty acid ester, polyoxy fatty acid ester, and polyoxyethylene alkylamine can be mentioned. These surfactants may be used alone or in combination of two or more.
[0196] When an additive is contained in a coating agent mainly composed of a polyvalent metal compound (B), the mass ratio of the polyvalent metal compound to the additive (polyvalent metal compound:additive) is preferably within the range of 30:70 to 99:1, and more preferably within the range of 50:50 to 98:2.
[0197] Examples of the solvent used in the coating agent containing polyvalent metal compound (B) as a main component include water, methyl alcohol, ethyl alcohol, isopropyl alcohol, n-propyl alcohol, n-butyl alcohol, n-pentyl alcohol, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, toluene, hexane, heptane, cyclohexane, acetone, methyl ethyl ketone, diethyl ether, dioxane, tetrahydrofuran, ethyl acetate, and butyl acetate. These solvents may be used alone or in combination of two or more. Among these, from the viewpoint of coating property, methyl alcohol, ethyl alcohol, isopropyl alcohol, toluene, ethyl acetate, methyl ethyl ketone, and water are preferred. From the viewpoint of manufacturability, methyl alcohol, ethyl alcohol, isopropyl alcohol, and water are preferred.
[0198] When a coating agent containing a polycarboxylic acid polymer (A) and a polyvalent metal compound (B) is applied and dried to form a polycarboxylic acid polyvalent metal salt film, the polycarboxylic acid polymer (A) and the polyvalent metal compound (B) are mixed with a resin or dispersant that can be dissolved or dispersed in water or alcohol as a solvent, and additives as necessary, and the mixture is applied and dried by a known coating method to form a polycarboxylic acid polyvalent metal salt film. Examples of the coating method include casting, dipping, roll coating, gravure coating, screen printing, reverse coating, spray coating, kit coating, die coating, metaling bar coating, chamber doctor combined coating, curtain coating, etc.
[0199] The thickness of the oxygen barrier film 130 is set according to the required oxygen barrier properties, and may be, for example, 0.05 to 5 μm. The thickness of the oxygen barrier film 130 is preferably 0.05 to 1 μm, and more preferably 0.1 to 0.5 μm. If the thickness of the oxygen barrier film 130 is 0.05 μm or more, sufficient oxygen barrier properties are easily obtained. If the thickness of the oxygen barrier film 130 is 1 μm or less, it is easy to form a uniform coating surface, and drying load and production costs can be suppressed.
[0200] In the oxygen barrier coating 130, a gas barrier film having the organic-inorganic composite coating or the polyvalent metal salt coating of polycarboxylic acid exhibits excellent oxygen barrier properties even when subjected to boiling or retort sterilization, and when laminated with a sealant film, has sufficient adhesion strength and sealing strength even when used as a packaging material for boiling or retort treatment. Furthermore, it has advantages such as transparency not found in metal foils or metal vapor-deposited films, excellent bending resistance and stretching resistance, and no risk of generating harmful substances such as dioxins.
[0201] [Method of manufacturing gas barrier film] The gas barrier film 101 can be produced by forming either the underlayer 140 or the inorganic oxide layer 150, or both the underlayer 140 and the inorganic oxide layer 150, on the first surface 21 of the resin substrate 120, and then forming the oxygen barrier coating 130 on the underlayer 140 or the inorganic oxide layer 150. The method for producing the gas barrier film 101 of the present disclosure includes, for example, a selection step, an underlayer forming step, an inorganic oxide layer forming step, and an oxygen barrier coating forming step.
[0202] In the selection process, for example, the number of protrusions on the surface with a Feret diameter of 8 μm or more is 20 / mm 2 The resin substrate raw roll is selected as the resin substrate 120. The number of protrusions on the surface of the resin substrate raw roll is measured in the same manner as the method for measuring the number of protrusions on the first surface 21 of the resin substrate 120 described above. The resin substrate 120 may be a commercially available product, or may be manufactured by a known method. It's fine.
[0203] An example of the underlayer forming step is a step of applying a coating agent to at least the first surface 21 of the resin substrate 120 by a wet coating method to form a coating film, and drying the coating film (removing the solvent) to form the underlayer 140. A known wet coating method can be used as a method for applying the coating agent. Examples of the wet coating method include roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating. Examples of the method for drying the coating film made of the coating agent include known drying methods such as hot air drying, hot roll drying, and infrared irradiation. Examples of drying conditions include a condition of 90°C for 10 seconds.
[0204] The inorganic oxide layer forming process may be, for example, a process of forming an inorganic oxide layer 150 on the first surface 21 of the resin substrate 120 or on the underlayer 140 by the above-mentioned vacuum deposition method, sputtering method, ion plating method, plasma chemical vapor deposition (CVD), or the like.
[0205] The oxygen barrier film forming step may be, for example, a step of forming a coating film by applying a coating agent on the underlayer 140 or the inorganic oxide layer 150 by a wet coating method, and drying the coating film (removing the solvent) to form the oxygen barrier film 130. A known wet coating method may be used as a method for applying the coating agent. Examples of the wet coating method include roll coating, gravure coating, reverse coating, die coating, screen printing, and spray coating. A known drying method such as hot air drying, hot roll drying, and infrared irradiation may be used as a method for drying the coating film made of the coating agent. Examples of drying conditions include conditions at 90° C. for 10 seconds. The oxygen barrier film 130 may be formed by applying and drying once, or by repeatedly applying and drying the same or different coating agents multiple times.
[0206] When the manufacturing method of the gas barrier film 101 of the present disclosure includes a selection step, the number of protrusions having a Feret's diameter of 8 μm or more on the surface is 20 / mm 2 The resin base material 120 described below can be efficiently used. Therefore, by having the selection process, a gas barrier film with improved oxygen barrier properties can be efficiently produced. In addition, by having the selection process, a gas barrier film 101 with good printability can be efficiently produced.
[0207] The gas barrier film 101 of the present disclosure may further have a printing layer, a protective layer, a light-shielding layer, an adhesive layer, a heat-sealable heat-fusible layer, other functional layers, etc., as necessary. When the gas barrier film 101 of the present disclosure has a heat-sealable heat-fusible layer, this heat-fusible layer is disposed on at least one outermost layer of the gas barrier film 101. By having the heat-fusible layer in the gas barrier film 101, the gas barrier film 101 becomes a film that can be sealed by heat sealing (for example, a package or a lid). The heat-fusible layer can be laminated, for example, on a laminate obtained by forming the undercoat layer 140, inorganic oxide layer 150, and oxygen barrier film 130 of the present embodiment on one or both sides of the resin substrate 120, using a known adhesive such as a polyurethane-based, polyester-based, or polyether-based adhesive, by a known dry lamination method, extrusion lamination method, or the like.
[0208] <Action and effect> In the gas barrier film 101 of the present disclosure, the resin layer forming the first surface 21 is made of a polyolefin copolymer resin, and the first surface has protrusions with a Feret's diameter of 8 μm or more measured by the above-mentioned measurement method of 20 protrusions / mm 2 On the first surface 21 of the resin substrate 120 described below, either the undercoat layer 140 or the inorganic oxide layer 150, or both the undercoat layer 140 and the inorganic oxide layer 150, are laminated, and further, an oxygen barrier coating 130 is laminated. In the gas barrier film 101 of the present disclosure, the surface layer 23 is made of a polyolefin copolymer resin, and protrusions having a Feret's diameter of 8 μm or more are formed at a rate of 20 / mm 2Since the oxygen barrier film 130 is formed on the resin substrate 120 described below via either the underlayer 140 or the inorganic oxide layer 150 or both, film defects caused by large protrusions on the substrate surface are unlikely to occur, the oxygen barrier properties can be improved, and the adhesion of the oxygen barrier film 130 can be improved. In addition, the gas barrier film 101 of the present disclosure does not need to increase the thickness of the underlayer 140, the inorganic oxide layer 150, and the oxygen barrier film 130 unnecessarily, so that productivity can be improved and the amount of material used can be reduced. Therefore, by using the gas barrier film 101 of the present disclosure as a packaging material, it has sufficient lamination strength as a packaging material and can inexpensively improve the quality retention of the contents. EXAMPLES
[0209] The following examples and comparative examples are examples of the present disclosure. Attitude The present disclosure will be described in more detail below, but is not limited to the following examples.
[0210] The materials used in the following examples are listed below. [Materials used] <Resin substrate> α1: Biaxially oriented polypropylene film (product name: M-1, thickness 20 μm, one-sided corona treatment, manufactured by Mitsui Chemicals Tohcello Co., Ltd.). α2: Biaxially oriented polypropylene film (product name: ME-1, thickness 20 μm, one-sided corona treatment, manufactured by Mitsui Chemicals Tohcello Co., Ltd.). α3: Biaxially oriented polypropylene film (product name: TS18TI-TPN, thickness 18 μm, one-sided corona treatment, manufactured by Max Speciality Films Limited). α4: Biaxially oriented polypropylene film (product name: P2111, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α5: Biaxially oriented polypropylene film (product name: P2171, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α6: Biaxially oriented polypropylene film (product name: P2102, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α7: Biaxially oriented polypropylene film (product name: P2161, thickness 20 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α8: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, one side corona treated, average particle size of AB agent on the corona treated side 2 μm, manufactured by AJPlast). α9: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, one side corona treated, average particle size of AB agent on the corona treated side 4 μm, manufactured by AJPlast). α10: Biaxially oriented polypropylene film (product name: PB210J, thickness 20 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α11: Polyethylene terephthalate film (product name: P60, thickness 12 μm, one-sided corona treatment, manufactured by Toray Industries, Inc.). α12: Polyethylene terephthalate film (product name: E5102, thickness 12 μm, one-sided corona treatment, manufactured by Toyobo Co., Ltd.). α13: Polyethylene film (product name: HD, thickness 40 μm, one-sided corona treatment, manufactured by Tamapoly Co., Ltd.). α14: Polyethylene film (product name: HS31, thickness 30 μm, one-sided corona treatment, manufactured by Tamapoly Co., Ltd.). α15: Linear low-density polyethylene film (product name: UB-3, thickness 40 μm, one-sided corona treatment, manufactured by Tamapoly Co., Ltd.). α16: Polyethylene film (product name: PE3K-H, thickness 25 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α17: Polyethylene film (product name: PE3M, thickness 25 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α18: Linear low-density polyethylene film (product name: LL-XHT, thickness 25 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α19: Linear low-density polyethylene film (product name: LL-RP2, thickness 25 μm, one-sided corona treatment, manufactured by Futamura Chemical Co., Ltd.). α20: Polyethylene film (thickness 25 μm, one side corona treated, manufactured by WINPAK Limited).
[0211] <Production Example 1> Acrylic polyol Acrydic CL-1000 (manufactured by DIC Corporation) was used as the acrylic polyol, and the TDI type curing agent Coronate 2030 (manufactured by Tosoh Corporation) was used as the isocyanate compound. The acrylic polyol and isocyanate compound were mixed in a solids weight ratio of 6:4, and a dilution solvent (ethyl acetate) was used to prepare a mixed liquid (solids content: 2% by mass) for forming the undercoat layer.
[0212] <Production Example 2> 20 parts by mass of an aqueous solution of polyacrylic acid having a number average molecular weight of 200,000 (Aron A-10H, manufactured by Toagosei Co., Ltd., solid content concentration 25% by mass) was diluted with 58.9 parts by mass of distilled water. Then, 0.44 parts by mass of aminopropyltrimethoxysilane (APTMS, manufactured by Aldrich Co., Ltd.) was added and stirred to obtain a uniform solution, thereby preparing a coating agent mainly composed of a polycarboxylic acid polymer.
[0213] <Production Example 3> A coating agent containing a polyvalent metal compound as a main component was prepared by mixing 100 parts by mass of an aqueous dispersion of zinc oxide particles (ZE143 manufactured by Sumitomo Osaka Cement) and 2 parts by mass of a hardener Liofol HAERTER UR 5889-21 (manufactured by Henkel).
[0214] <Production Example 4> An aqueous solution of polyvinyl alcohol resin (PVA, product name: Poval PVA-105, manufactured by Kuraray Co., Ltd., polyvinyl alcohol with a degree of saponification of 98-99% and a degree of polymerization of 500) was dissolved, and an aqueous solution of tetraethoxysilane (TEOS) and γ-glycidoxypropyltrimethoxysilane (GPTMS, product name: KBM-403, manufactured by Shin-Etsu Chemical Co., Ltd.) was hydrolyzed with 0.02 mol / L hydrochloric acid, respectively, and the aqueous solutions were mixed so that the weight ratio of PVA:TEOS:GPTMS before hydrolysis was 40:50:10. Furthermore, a dilution solvent was added so that the solvent components of the mixed aqueous solution had a mass ratio of water:isopropyl alcohol of 90:10, and a coating agent (5 mass%) for forming an organic-inorganic composite film was prepared.
[0215] [Measurement of the black area ratio of resin substrate] The black area ratio was determined for the corona-treated surface of each of the resin substrates α1 to 12 under the image acquisition conditions and image analysis conditions described above. The results are shown in Table 1. The black area ratio was measured using an optical microscope OLS-4000 manufactured by Olympus Corporation, a 10x objective lens (MPFLN10), and Scion ImageJ from Scion Corporation as image analysis software.
[0216] [Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-4] On the corona-treated surface of the resin substrate described in Table 1, the mixed solution for forming the undercoat layer prepared in Production Example 1 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, on the formed undercoat layer, a coating agent mainly composed of a polycarboxylic acid polymer prepared in Production Example 2 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polycarboxylic acid polymer film, and further, on the polycarboxylic acid polymer film, a coating agent mainly composed of a polyvalent metal compound prepared in Production Example 3 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polyvalent metal compound film, thereby forming an oxygen barrier film consisting of a polyvalent metal salt film of polycarboxylic acid, and the gas barrier films of Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-4 were obtained.
[0217] <Printability evaluation> Black ink (product name: N920LPGT, manufactured by Toyo Ink Co., Ltd.) was printed in gradation on the oxygen barrier coating of the gas barrier film of each example using a gravure printer with a halftone dot density of 5% to 50% (in 5% increments). The ink viscosity was 14 seconds (Zahn cup #3, 25°C). The printing speed was 150 m / min, and the drying temperature was 50°C. The surface after printing was observed with an optical microscope, and the number of missing dots was counted. The evaluation was as follows: if there were less than 5 missing dots in a 6 mm square area, it was marked as O; if there were 5 to 20 missing dots, it was marked as △; if there were 21 or more missing dots, it was marked as ×. The evaluation results are shown in Table 1.
[0218] "Missing dots" refers to a state in which the ink does not adhere well to the film substrate, resulting in some dots (halftone dots) not being transferred. The fewer the missing dots, even at low halftone dot densities, the better the printability of the highlights.
[0219] <Evaluation of oxygen barrier property and water vapor barrier property after retort treatment> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort processing with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40°C for 3 days. The oxygen barrier coating of the gas barrier film was placed on the adhesive side.
[0220] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization treatment (retort treatment) in hot water at 120° C. for 30 minutes.
[0221] The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The results are shown in Table 1.
[0222] [Table 1]
[0223] From the results shown in Table 1, the gas barrier films of Examples 1-1 to 1-8 had a black area ratio of 0.15% or less and an oxygen permeability of 2 cm or less in an atmosphere of 30° C. and 70% relative humidity. 3 / (m 2 Good oxygen barrier properties were obtained at temperatures below 100°C (day atm).
[0224] On the other hand, the gas barrier films of Comparative Examples 1-1 to 1-4 have a black area ratio of 0.15% or more and an oxygen permeability value of 2 cm 3 / (m 2 The black area ratio exceeded 0.15%, which resulted in an increase in oxygen permeability, and as a result, good oxygen barrier properties were not obtained as compared with Examples 1-1 to 1-8.
[0225] From the results shown in Table 1, the gas barrier films of Examples 1-1 to 1-8 were rated "good" for printability when the dot density was 30% or more.
[0226] On the other hand, the gas barrier films of Comparative Examples 1-1 to 1-4 were rated "x" for printability at a dot density of 30%.
[0227] Thus, it was found that printability was good when the black area ratio was 0.15% or less.
[0228] [Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4] On the corona-treated surface of the resin substrate shown in Table 2, the mixed solution for forming the undercoat layer prepared in Production Example 1 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, a vacuum deposition device using an electron beam heating method was used to evaporate a mixed material containing two or more of metal silicon, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer made of silicon oxide having a thickness of 30 nm on the undercoat layer. Next, the coating agent for forming the organic-inorganic composite coating prepared in Production Example 4 was applied using a gravure printer to the inorganic oxide layer formed to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming an oxygen barrier coating made of an organic-inorganic composite coating having a thickness of 0.3 μm, thereby obtaining gas barrier films of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-4.
[0229] [Example 2-7] A gas barrier film of Example 2-7 was obtained in the same manner as in Example 2-3, except that an inorganic oxide layer was formed directly on the corona-treated surface of the resin substrate α8 without providing an undercoat layer.
[0230] <Printability evaluation> A black ink (product name: N920LPGT, manufactured by Toyo Ink Co., Ltd.) was printed in gradation on the oxygen barrier coating of the gas barrier film of each example using a gravure printer with a halftone dot density of 5% to 50% (in 5% increments). The ink viscosity was 14 seconds (Zahn cup #3, 25°C). The printing speed was 150 m / min, and the drying temperature was 50°C. The surface after printing was observed with an optical microscope, and the number of missing dots was counted. The evaluation was as follows: if there were less than 5 missing dots in a 6 mm square area, it was marked as O; if there were 5 to 20 missing dots, it was marked as △; if there were 21 or more missing dots, it was marked as ×. The evaluation results are shown in Table 2.
[0231] "Missing dots" refers to a state in which the ink does not adhere well to the film substrate, resulting in some dots (halftone dots) not being transferred. The fewer the missing dots, even at low halftone dot densities, the better the printability of the highlights.
[0232] <Evaluation of oxygen barrier property and water vapor barrier property after retort treatment> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort processing with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40°C for 3 days. The oxygen barrier coating of the gas barrier film was placed on the adhesive side.
[0233] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization treatment (retort treatment) in hot water at 120° C. for 30 minutes.
[0234] The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The results are shown in Table 2.
[0235] [Table 2]
[0236] From the results shown in Table 2, the gas barrier films of Examples 2-1 to 2-7 had a black area ratio of 0.15% or less and an oxygen permeability value of 3 cm or less in an atmosphere of 30° C. and 70% relative humidity. 3 / (m 2Good oxygen barrier properties were obtained at temperatures below 100°C (day atm).
[0237] On the other hand, the gas barrier films of Comparative Examples 2-1 to 2-4 have a black area ratio of 0.15% or more and an oxygen permeability value of 5 cm 3 / (m 2 The black area ratio exceeded 0.15%, which resulted in an increase in oxygen permeability, and as a result, good oxygen barrier properties were not obtained as compared with Examples 2-1 to 2-7.
[0238] From the results shown in Table 2, the gas barrier films of Examples 2-1 to 2-7 were rated "good" for printability when the dot density was 30% or more.
[0239] On the other hand, the gas barrier films of Comparative Examples 2-1 to 2-4 were rated "x" for printability at a dot density of 30%.
[0240] Thus, it was found that printability was good when the black area ratio was 0.15% or less.
[0241] [Examples 3-1 to 3-7 and Comparative Example 3-1] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 3 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, a vacuum deposition apparatus using an electron beam heating system was used to evaporate a mixed material containing two or more of silicon metal, silicon monoxide, and silicon dioxide, to form an inorganic oxide layer made of silicon oxide and having a thickness of 30 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film consisting of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 3-1 to 3-7 and Comparative Example 3-1 were obtained.
[0242] [Examples 3-8] A gas barrier film of Example 3-8 was obtained in the same manner as in Example 3-4, except that an inorganic oxide layer was formed directly on the corona-treated surface of the resin substrate α8 without providing an undercoat layer.
[0243] <Printability evaluation> A black ink (product name: N920LPGT, manufactured by Toyo Ink Co., Ltd.) was printed in gradation on the oxygen barrier coating of the gas barrier film of each example using a gravure printer with a halftone dot density of 5% to 50% (in 5% increments). The ink viscosity was 14 seconds (Zahn cup #3, 25°C). The printing speed was 150 m / min, and the drying temperature was 50°C. The surface after printing was observed with an optical microscope, and the number of missing dots was counted. The evaluation was as follows: if there were less than 5 missing dots in a 6 mm square area, it was marked as O; if there were 5 to 20 missing dots, it was marked as △; if there were 21 or more missing dots, it was marked as ×. The evaluation results are shown in Table 3.
[0244] "Missing dots" refers to a state in which the ink does not adhere well to the film substrate, resulting in some dots (halftone dots) not being transferred. The fewer the missing dots, even at low halftone dot densities, the better the printability of the highlights.
[0245] <Evaluation of oxygen barrier property and water vapor barrier property after retort treatment> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort processing with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40°C for 3 days. The oxygen barrier coating of the gas barrier film was placed on the adhesive side.
[0246] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization treatment (retort treatment) in hot water at 120° C. for 30 minutes.
[0247] The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The results are shown in Table 3.
[0248] [Table 3]
[0249] From the results shown in Table 3, the gas barrier films of Examples 3-1 to 3-8 had a black area ratio of 0.15% or less and an oxygen permeability of 2 cm or less in an atmosphere of 30° C. and 70% relative humidity. 3 / (m 2 Good oxygen barrier properties were obtained at temperatures below 100°C (day atm).
[0250] On the other hand, the gas barrier film of Comparative Example 3-1 had a black area ratio of 0.15% or more and an oxygen permeability value of 4.7 cm 3 / (m 2 ·day·atm) and Examples 3-1 to 3-8 In comparison, good oxygen barrier properties were not obtained.
[0251] From the results shown in Table 3, the gas barrier films of Examples 3-1 to 3-8 were rated "good" for printability when the dot density was 30% or more.
[0252] On the other hand, the gas barrier film of Comparative Example 3-1 was rated "x" for printability at a dot density of 30%.
[0253] Thus, it was found that printability was good when the black area ratio was 0.15% or less.
[0254] [Examples 4-1 to 4-5 and Comparative Example 4-1] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 4 using a gravure printer to form a coating film, which was then passed through a 100°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, metallic aluminum was evaporated using a vacuum deposition device using an electron beam heating system, and oxygen gas was introduced therein to form an inorganic oxide layer made of aluminum oxide with a thickness of 20 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film consisting of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 4-1 to 4-5 and Comparative Example 4-1 were obtained.
[0255] [Examples 4-6] A gas barrier film of Example 4-6 was obtained in the same manner as in Example 4-2, except that an inorganic oxide layer was formed directly on the corona-treated surface of the resin substrate α8 without providing an undercoat layer.
[0256] <Printability evaluation> A black ink (product name: N920LPGT, manufactured by Toyo Ink Co., Ltd.) was printed in gradation on the oxygen barrier coating of the gas barrier film of each example using a gravure printer with a halftone dot density of 5% to 50% (in 5% increments). The ink viscosity was 14 seconds (Zahn cup #3, 25°C). The printing speed was 150 m / min, and the drying temperature was 50°C. The surface after printing was observed with an optical microscope, and the number of missing dots was counted. The evaluation was as follows: if there were less than 5 missing dots in a 6 mm square area, it was marked as O; if there were 5 to 20 missing dots, it was marked as △; if there were 21 or more missing dots, it was marked as ×. The evaluation results are shown in Table 4.
[0257] "Missing dots" refers to a state in which the ink does not adhere well to the film substrate, resulting in some dots (halftone dots) not being transferred. The fewer the missing dots, even at low halftone dot densities, the better the printability of the highlights.
[0258] <Evaluation of oxygen barrier property and water vapor barrier property after retort treatment> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort processing with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40°C for 3 days. The oxygen barrier coating of the gas barrier film was placed on the adhesive side.
[0259] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization treatment (retort treatment) in hot water at 120° C. for 30 minutes.
[0260] The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The results are shown in Table 4.
[0261] [Table 4]
[0262] From the results shown in Table 4, the gas barrier films of Examples 4-1 to 4-6 had a black area ratio of 0.15% or less and an oxygen permeability of 1 cm or less in an atmosphere of 30° C. and 70% relative humidity. 3 / (m 2 On the other hand, the gas barrier film of Comparative Example 4-1 had a black area ratio of 0.15% or more and an oxygen permeability of 1.5 cm 3 / (m 2 ·day·atm), no good oxygen barrier property was obtained compared with Examples 4-1 to 4-6.
[0263] From the results shown in Table 4, the gas barrier films of Examples 4-1 to 4-6 were rated "good" for printability when the dot density was 30% or more.
[0264] On the other hand, the gas barrier film of Comparative Example 4-1 was rated "x" for printability at a dot density of 30%.
[0265] Thus, it was found that printability was good when the black area ratio was 0.15% or less.
[0266] [Examples 5-1 to 5-5 and Comparative Examples 5-1 to 5-3] The mixed solution for forming the undercoat layer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate described in Table 5 using a gravure printer to form a coating film, and the coating film was passed through an oven at 60°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, a vacuum deposition device using an electron beam heating system was used to evaporate a mixed material containing two or more of metal silicon, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer made of silicon oxide having a thickness of 30 nm on the undercoat layer. Next, the coating agent for forming the organic-inorganic composite coating prepared in Production Example 4 was applied to the inorganic oxide layer formed using a gravure printer to form a coating film, and the coating film was passed through an oven at 60°C for 10 seconds to dry, thereby forming an oxygen barrier coating made of an organic-inorganic composite coating having a thickness of 0.3 μm, thereby obtaining gas barrier films of Examples 5-1 to 5-5 and Comparative Examples 5-1 to 5-3.
[0267] [Examples 5-6] A gas barrier film of Example 5-6 was obtained in the same manner as in Example 5-2, except that an inorganic oxide layer was formed directly on the corona-treated surface of the resin substrate α14 without providing an undercoat layer.
[0268] [Examples 5-7 to 5-11 and Comparative Examples 5-4 to 5-6] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 5 using a gravure printer to form a coating film, which was then passed through a 60°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, metallic aluminum was evaporated using a vacuum deposition device using an electron beam heating system, and oxygen gas was introduced therein to form an inorganic oxide layer made of aluminum oxide with a thickness of 20 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in a 60°C oven for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in a 50°C oven for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film consisting of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 5-7 to 5-11 and Comparative Examples 5-4 to 5-6 were obtained.
[0269] [Example 5-12] A gas barrier film of Example 5-12 was obtained in the same manner as in Example 5-8, except that an inorganic oxide layer was formed directly on the corona-treated surface of the resin substrate α14 without providing an undercoat layer.
[0270] [Example 5-13] A gas barrier film of Example 5-13 was obtained in the same manner as in Example 5-8, except that a polyvalent metal compound film was formed on the undercoat layer formed on the corona-treated surface of the resin substrate α14 without providing an inorganic oxide layer.
[0271] <Evaluation of oxygen barrier property and water vapor barrier property before and after boiling treatment> The gas barrier film of each example was laminated with LLDPE (polyethylene film) using an adhesive to produce a gas barrier laminated film for boiling treatment with a gas barrier film / adhesive / LLDPE structure. The adhesive used was a two-part curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the LLDPE was a polyethylene film made by Mitsui Chemicals Tohcello, TUX MC-S (60μm). Dry lamination was performed using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40℃ for 3 days. The oxygen barrier coating of the gas barrier film was placed so that it was on the adhesive side.
[0272] The resulting gas barrier laminate film was used to prepare an A5-sized pouch with four sides sealed, which was filled with 150 ml of tap water and subjected to heat sterilization (boiling) in hot water at 90° C. for 30 minutes.
[0273] The gas barrier laminate film before and after the boiling treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The results are shown in Table 5.
[0274] [Table 5]
[0275] From the results shown in Table 5, the gas barrier films of Examples 5-1 to 5-6 had a black area ratio of 0.15% or less, and an oxygen permeability value of 2 cm before boiling in an atmosphere of 30° C. and relative humidity of 70%. 3 / (m2 ·day·atm) or less, after boiling 3cm 3 / (m 2 1·day·atm) or less, and good oxygen barrier properties were obtained.
[0276] The gas barrier films of Examples 5-7 to 5-13 had a black area ratio of 0.15% or less, and the oxygen permeability values in an atmosphere of 30° C. and 70% relative humidity were 1 cm 3 / (m 2 1·day·atm) or less, and good oxygen barrier properties were obtained.
[0277] On the other hand, the gas barrier films of Comparative Examples 5-1 to 5-3 have a black area ratio of 0.15% or more and an oxygen permeability of 2 cm before boiling. 3 / (m 2 ·day·atm) or more, 3cm after boiling 3 / (m 2 ·day·atm) or more, and good oxygen barrier properties were not obtained.
[0278] The gas barrier films of Comparative Examples 5-4 to 5-6 had a black area ratio of 0.15% or more and an oxygen permeability value of 1 cm 3 / (m 2 ·day·atm) or more, and good oxygen barrier properties were not obtained.
[0279] [Examples 6-1 to 6-4 and Comparative Examples 6-1 to 6-5] In Examples 6-1 to 6-4 and Comparative Examples 6-1 to 6-5, the influence of the production lot of the resin substrate was examined.
[0280] On the corona-treated surface of the resin substrate shown in Table 6A, the mixed solution for forming the undercoat layer prepared in Production Example 1 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, on the formed undercoat layer, the coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polycarboxylic acid polymer film, and further, on the polycarboxylic acid polymer film, the coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polyvalent metal compound film, thereby forming an oxygen barrier film consisting of a polyvalent metal salt film of polycarboxylic acid, and the gas barrier films of Experimental Examples 6-1 to 6-4 and Comparative Examples 6-1 to 6-5 were obtained.
[0281] [Examples 6-5 to 6-8 and Comparative Examples 6-6 to 6-10] The mixed solution for forming the undercoat layer prepared in Production Example 1 was applied to the corona-treated surface of the resin substrate shown in Table 6B using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, a vacuum deposition device using an electron beam heating system was used to evaporate a mixed material containing two or more of metal silicon, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer made of silicon oxide having a thickness of 30 nm on the undercoat layer. Next, the coating agent for forming the organic-inorganic composite coating prepared in Production Example 4 was applied to the inorganic oxide layer formed using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming an oxygen barrier coating made of an organic-inorganic composite coating having a thickness of 0.3 μm, thereby obtaining gas barrier films of Examples 6-5 to 6-8 and Comparative Examples 6-6 to 6-10.
[0282] The black area ratio, oxygen permeability and printability of the resin substrate were evaluated in the same manner as in Examples 1-1 to 1-8. The measurement results are shown in Tables 6A and 6B.
[0283] [Table 6A]
[0284] [Table 6B] First, the resin substrates used in Examples 6-1 to 6-4 and Comparative Example 6-1 have the same material, product number, manufacturer, and thickness, but different production lots. Similarly, the resin substrates used in Examples 6-5 to 6-8 and Comparative Example 6-6 have the same material, product number, manufacturer, and thickness, but different production lots. However, the black area ratios of the resin substrates measured by the above-mentioned method were different for each production lot. That is, from the measurement results of the black area ratios shown in Tables 6A and 6B, it was confirmed that the black area ratios measured by the above-mentioned method were not specific to the type of resin substrate (α8 or α9), but varied depending on the production lot.
[0285] Next, from the results shown in Tables 6A and 6B, the gas barrier films according to Examples 6-1 to 6-4 and Examples 6-5 to 6-8 (the black area ratio of the resin substrate is 0.15% or less) exhibited good oxygen barrier properties in an atmosphere of 30°C and relative humidity of 70%, and the printability was evaluated as "○" at a dot density of 30% or more. In contrast, the gas barrier film according to Comparative Example 6-1 had a black area ratio of the resin substrate exceeding 0.15%, and had a high oxygen permeability and poor printability compared to Examples 6-1 to 6-4 of the same configuration. Similarly, the gas barrier film according to Comparative Example 6-6 also had a black area ratio of the resin substrate exceeding 0.15%, and had a high oxygen permeability and poor printability compared to Examples 6-5 to 6-8 of the same configuration.
[0286] These results demonstrate that, even when gas barrier films of the same configuration are constructed using the same type of resin substrate, differences in performance of the gas barrier films arise depending on the production lot of the resin substrate. However, it has been confirmed that the effects of the production lot of the resin substrate can be reduced if the black area ratio of the resin substrate is 0.15% or less.
[0287] Hereinafter, the second embodiment of the present disclosure will be described in more detail with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples. The materials used in the following examples are shown below.
[0288] [Materials used] <Resin substrate> β1: Biaxially oriented polypropylene film (product name: ME-1, thickness 20 μm, surface layer is polyolefin copolymer resin, manufactured by Mitsui Chemicals Tocello Inc.). β2: Biaxially oriented polypropylene film (product name: P2111, thickness 20 μm, surface layer is polyolefin copolymer resin, manufactured by Toyobo Co., Ltd.). β3: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, surface layer is polyolefin copolymer resin, contains AB agent with average particle size of 2 μm, manufactured by AJPlast). β4: Biaxially oriented polypropylene film (product name: VPH2011, thickness 20 μm, surface layer is polyolefin copolymer resin, contains AB agent with average particle size of 4 μm, manufactured by AJPlast). β5: Biaxially oriented polypropylene film (product name: TS19TIMCP, thickness 19 μm, surface layer is polyolefin copolymer resin, manufactured by Max Speciality Films Limited). β6: Biaxially oriented polypropylene film (product name: TS18TIV, thickness 18 μm, surface layer is polyolefin copolymer resin, manufactured by Max Speciality Films Limited). β7: Biaxially oriented polypropylene film (product name: TS18TI-TPN, thickness 18 μm, surface layer is polypropylene homopolymer, manufactured by Max Speciality Films Limited). β8: Biaxially oriented polypropylene film (product name: M-1, thickness 20 μm, surface layer is polypropylene homopolymer, manufactured by Mitsui Chemicals Tocello Inc.).
[0289] [Measurement of the number of protrusions on the surface of a resin substrate] The number of protrusions having a Feret's diameter of 8 μm or more was counted for each of the surfaces (first surfaces) of the resin substrates β1 to β8 on which the oxygen barrier film was to be formed, according to the measurement conditions described above. The results are shown in Tables 7 to 10.
[0290] [Examples 7-1 to 7-3 and Comparative Examples 7-1 to 7-5] A coating film was formed on the first surface of the resin substrate described in Table 7 by using a gravure printer by applying the mixed solution for forming the undercoat layer prepared in Production Example 1, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, a vacuum deposition device using an electron beam heating system was used to evaporate a mixed material containing two or more of metal silicon, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer of silicon oxide having a thickness of 30 nm on the undercoat layer. Next, a coating agent for forming the organic-inorganic composite coating prepared in Production Example 4 was applied on the formed inorganic oxide layer by using a gravure printer to form a coating film, and the coating film was passed through an oven at 100°C for 10 seconds to dry, thereby forming an oxygen barrier coating film of an organic-inorganic composite coating having a thickness of 0.3 μm, thereby obtaining gas barrier films of Examples 7-1 to 7-3 and Comparative Examples 7-1 to 7-5.
[0291] [Example 7-4] A gas barrier film of Example 7-4 was obtained in the same manner as in Example 7-3, except that an inorganic oxide layer was formed directly on the first surface of the resin substrate β3 without providing an undercoat layer thereon.
[0292] <Oxygen barrier properties, water vapor barrier properties, and laminate strength evaluation after retort processing> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort treatment with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP used was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40 ° C for 3 days. The oxygen barrier film of the gas barrier film was arranged so that it was on the adhesive side. An A5 size four-sided sealed pouch was made with the obtained gas barrier laminate film, and 200 ml of tap water was filled as the contents, and heat sterilization treatment (retort treatment) was performed in hot water at 120 ° C for 30 minutes. The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 ·day) was measured. The measurement results are shown in Table 7. For the gas barrier laminate film after retort treatment, test pieces were cut into 15 mm wide rectangular pieces, and the laminate strength between the gas barrier film and the CPP film was measured using a universal testing machine Tensilon RTC-1250, peeling at a peel speed of 300 m / min, T-shaped and 180°. The measurement results are shown in Table 7.
[0293] [Table 7]
[0294] From the results shown in Table 7, it is found that the first surface of the resin substrate is a polyolefin copolymer resin, and the number of protrusions of 8 μm or more in Feret's diameter on the first surface of the resin substrate is 20 / mm 2The gas barrier films of Examples 7-1 to 7-4 shown below have an oxygen permeability of 3 cm or less under an atmosphere of 30° C. and 70% RH. 3 / (m 2 ·day·atm), and has a water vapor transmission rate of 1g / (m 2 On the other hand, the number of protrusions with a Feret's diameter of 8 μm or more on the first surface of the resin substrate was 20 / mm 2 The gas barrier films of Comparative Examples 7-1 to 7-3, which have oxygen permeability values exceeding 3 cm 3 / (m 2 ·day·atm) and has a water vapor transmission rate of 1g / (m 2 The oxygen barrier property and water vapor barrier property were inferior.
[0295] From the results shown in Table 7, Comparative Examples 7-4 to 7-5, in which the first surface of the resin substrate is a polypropylene homopolymer, have a laminate strength of less than 2N / 15mm after retort treatment, which is insufficient, whereas Examples 7-1 to 7-4, in which the first surface of the resin substrate is a polyolefin copolymer resin, have a sufficient laminate strength of 2N / 15mm or more even after retort treatment. In particular, Example 7-4 showed good laminate strength even without a base layer. In addition, "substrate break" in Table 7 indicates that the resin substrate broke at a strength of 2N / 15mm or more without peeling between the gas barrier film and the CPP film, which indicates that the laminate strength is sufficiently high.
[0296] [Examples 8-1 to 8-3 and Comparative Examples 8-1 to 8-3] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the first surface of the resin substrate shown in Table 8 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, thereby forming an underlayer having a thickness of 0.1 µm. Next, a vacuum deposition apparatus using an electron beam heating system was used to evaporate a mixed material containing two or more of silicon metal, silicon monoxide, and silicon dioxide, thereby forming an inorganic oxide layer made of silicon oxide having a thickness of 30 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film composed of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Examples 8-1 to 8-3 and Comparative Examples 8-1 to 8-3 were obtained.
[0297] [Example 8-4] A gas barrier film of Example 8-4 was obtained in the same manner as in Example 8-3, except that an inorganic oxide layer was formed directly on the first surface of the resin substrate β3 without providing an undercoat layer.
[0298] <Oxygen barrier properties, water vapor barrier properties, and laminate strength evaluation after retort processing> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort treatment with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), dry laminated with a multi-coater TM-MC made by HIRANO TECSEED, and cured at 40 ° C for 3 days. The oxygen barrier film of the gas barrier film was arranged so that it was on the adhesive side. An A5 size four-sided seal pouch was made with the obtained gas barrier laminate film, and 200 ml of tap water was filled as the contents, and heat sterilization treatment (retort treatment) was performed in hot water at 120 ° C for 30 minutes. The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 ·day) was measured. The measurement results are shown in Table 8. For the gas barrier laminate film after retort treatment, test pieces were cut into 15 mm wide rectangular pieces, and the lamination strength between the gas barrier film and the CPP film was measured using a universal testing machine Tensilon RTC-1250, peeling at a peel speed of 300 m / min, T-shaped and 180°. The measurement results are shown in Table 8.
[0299] [Table 8]
[0300] From the results shown in Table 8, it is found that the first surface of the resin substrate is a polyolefin copolymer resin, and the number of protrusions of 8 μm or more in Feret's diameter on the first surface of the resin substrate is 20 / mm 2The gas barrier films of Examples 8-1 to 8-4 shown below have an oxygen permeability of 2 cm or more under an atmosphere of 30° C. and 70% RH. 3 / (m 2 On the other hand, the first surface of the resin substrate had 20 protrusions / mm2 with a Feret's diameter of 8 μm or more. 2 The gas barrier films of Comparative Examples 8-1 to 8-3, in which the first surface of the resin substrate is a polypropylene homopolymer, have an oxygen permeability of 2 cm 3 / (m 2 The oxygen barrier properties were poor at over 1000 MPa (1000 MPa).
[0301] From the results shown in Table 8, Comparative Examples 8-2 to 8-3, in which the first surface of the resin substrate is a polypropylene homopolymer, had a laminate strength of less than 2N / 15mm after retort treatment, which was insufficient, whereas Examples 8-1 to 8-4, in which the first surface of the resin substrate is a polyolefin copolymer resin, had a sufficient laminate strength of 2N / 15mm or more even after retort treatment. In particular, Example 8-4 showed good laminate strength even without a base layer.
[0302] [Examples 9-1 to 9-3 and Comparative Examples 9-1 to 9-3] On the first surface of the resin substrate described in Table 9, the mixture for forming the undercoat layer prepared in Production Example 1 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.1 μm thick undercoat layer. Next, on the formed undercoat layer, a coating agent mainly composed of a polycarboxylic acid polymer prepared in Production Example 2 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polycarboxylic acid polymer film, and further, on the polycarboxylic acid polymer film, a coating agent mainly composed of a polyvalent metal compound prepared in Production Example 3 was applied using a gravure printer to form a coating film, and the coating film was passed through an oven at 100 ° C. for 10 seconds to dry, thereby forming a 0.2 μm thick polyvalent metal compound film, thereby forming an oxygen barrier film consisting of a polyvalent metal salt film of polycarboxylic acid, and the gas barrier films of Examples 9-1 to 9-3 and Comparative Examples 9-1 to 9-3 were obtained.
[0303] <Oxygen barrier properties, water vapor barrier properties, and laminate strength evaluation after retort processing> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort treatment with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP used was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40 ° C for 3 days. The oxygen barrier film of the gas barrier film was arranged so that it was on the adhesive side. An A5 size four-sided sealed pouch was made with the obtained gas barrier laminate film, and 200 ml of tap water was filled as the contents, and heat sterilization treatment (retort treatment) was performed in hot water at 120 ° C for 30 minutes. The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 ·day) was measured. The measurement results are shown in Table 9. For the gas barrier laminate film after retort treatment, test pieces were cut into 15 mm wide rectangular pieces, and the lamination strength between the gas barrier film and the CPP film was measured using a universal testing machine Tensilon RTC-1250, peeling at a peel speed of 300 m / min, T-shaped and 180°. The measurement results are shown in Table 9.
[0304] [Table 9]
[0305] From the results shown in Table 9, it is found that the first surface of the resin substrate is a polyolefin copolymer resin, and the number of protrusions having a Feret's diameter of 8 μm or more on the first surface of the resin substrate is 20 / mm 2 The gas barrier films of Examples 9-1 to 9-3 shown below have an oxygen permeability of 2 cm or more under an atmosphere of 30° C. and 70% RH. 3 / (m 2 The laminate strength after retort treatment was also sufficient, at 2N / 15mm or more. On the other hand, the number of protrusions with a Feret's diameter of 8μm or more on the first surface of the resin substrate was 20 / mm 2 The gas barrier films of Comparative Examples 9-1 to 9-3, which have oxygen permeability values exceeding 2 cm 3 / (m 2 The oxygen barrier properties were poor at over 1000 MPa (1000 MPa).
[0306] [Example 10-1 and Comparative Example 10-1] The mixed solution for forming the underlayer prepared in Production Example 1 was applied to the first surface of the resin substrate shown in Table 10 using a gravure printer to form a coating film, and the coating film was passed through a 100°C oven for 10 seconds to dry, forming an underlayer with a thickness of 0.1 µm. Next, metallic aluminum was evaporated using a vacuum deposition apparatus using an electron beam heating system, and oxygen gas was introduced therein to form an inorganic oxide layer made of aluminum oxide with a thickness of 20 nm on the underlayer. Next, a coating agent mainly composed of the polycarboxylic acid polymer prepared in Production Example 2 was applied onto the inorganic oxide layer using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polycarboxylic acid polymer film with a thickness of 0.2 μm. Further, a coating agent mainly composed of the polyvalent metal compound prepared in Production Example 3 was applied onto the polycarboxylic acid polymer film using a gravure printer to form a coating film, and the film was dried in an oven at 100°C for 10 seconds to form a polyvalent metal compound film with a thickness of 0.2 μm. Thus, an oxygen barrier film consisting of a polyvalent metal salt of polycarboxylic acid was formed, and the gas barrier films of Example 10-1 and Comparative Example 10-1 were obtained.
[0307] <Oxygen barrier properties, water vapor barrier properties, and laminate strength evaluation after retort processing> The gas barrier film of each example was laminated with CPP (polypropylene film) using an adhesive to produce a gas barrier laminate film for retort treatment with a gas barrier film / adhesive / CPP configuration. The adhesive used was a two-liquid curing adhesive made by Mitsui Chemicals Polyurethane, Takelac A620 (base) / Takenate A65 (curing agent), and the CPP used was a polypropylene film made by Toray Film Processing, Torayfan ZK93KM (60 μm), which was dry laminated using a multi-coater TM-MC made by HIRANO TECSEED and cured at 40 ° C for 3 days. The oxygen barrier film of the gas barrier film was arranged so that it was on the adhesive side. An A5 size four-sided sealed pouch was made with the obtained gas barrier laminate film, and 200 ml of tap water was filled as the contents, and heat sterilization treatment (retort treatment) was performed in hot water at 120 ° C for 30 minutes. The gas barrier laminate film after retort treatment was measured for oxygen permeability (cm) under an atmosphere of 30°C and 70% RH using an oxygen permeability measuring device (product name: OXTRAN-2 / 20, manufactured by MOCON). 3 / (m 2 The water vapor permeability (g / (m 2 100 sq. m 3 ... 2 The lamination strength between the gas barrier film and the CPP film was measured at a peel speed of 300 m / min, T-shaped and 180° peeling angles using a Tensilon RTC-1250 universal testing machine. The measurement results are shown in Table 10. For the gas barrier laminate film after retort treatment, test pieces were cut into 15 mm wide rectangular pieces, and the lamination strength between the gas barrier film and the CPP film was measured using a Tensilon RTC-1250 universal testing machine. The measurement results are shown in Table 10.
[0308] [Table 10]
[0309] From the results shown in Table 10, it is found that the first surface of the resin substrate is a polyolefin copolymer resin, and the number of protrusions of 8 μm or more in Feret's diameter on the first surface of the resin substrate is 20 / mm 2The gas barrier film of Example 10-1 has an oxygen permeability of 2 cm or less under an atmosphere of 30° C. and 70% RH. 3 / (m 2 The gas barrier film of Comparative Example 10-1, in which the first surface of the resin substrate is a polypropylene homopolymer, showed good oxygen barrier properties of less than 2 N / 15 mm (T-peel) after retort treatment, and had sufficient laminate strength of 2 N / 15 mm or more. On the other hand, the gas barrier film of Comparative Example 10-1, in which the first surface of the resin substrate is a polypropylene homopolymer, showed insufficient strength after retort treatment, showing a laminate strength (T-peel) of less than 2 N / 15 mm. [Industrial Applicability]
[0310] The gas barrier film of the present disclosure stably exhibits excellent gas barrier properties, and exhibits excellent gas barrier properties even after retort treatment. In addition, the surface condition of the substrate film can be easily grasped, and the quality can be stabilized even when the oxygen barrier coating is made thin, which enables reduction in raw material costs.
[0311] In addition, the gas barrier film of the present disclosure has good printability, so that printing can be easily and beautifully applied to the surface of the gas barrier film.
[0312] The gas barrier film of the present disclosure can be suitably used, for example, as a packaging material, and can also be suitably used as a packaging material for boiling treatment and retort treatment. By using the gas barrier film of the present disclosure as a packaging material, the quality retention of the contents can be improved.
[0313] The gas barrier film of the present disclosure can also be used for purposes other than packaging materials, such as electronic device-related films, solar cell films, various functional films for fuel cells, and substrate films. [Explanation of symbols]
[0314] 1. Gas barrier film 10 Resin substrate 20 Oxygen barrier coating 30 Underlying layer 40 Inorganic oxide layer
Claims
1. A resin substrate; an oxygen barrier film provided on at least one surface of the resin substrate; a base layer and / or an inorganic oxide layer provided between the resin substrate and the oxygen barrier coating; The resin substrate is a polyethylene film, A gas barrier film, wherein one surface of the resin substrate has a black area ratio of 0.15% or less as measured by the following measurement method. <Measurement method> An arbitrary region of 1281 μm square on one side of the resin substrate is photographed with an optical microscope to obtain a photographed image of 1024 × 1024 pixels, and the photographed image is converted into a monochrome image of 256 gradations using image analysis software. A threshold value is set to a value obtained by subtracting 30 from the most frequent brightness value in the monochrome image, and the brightness is binarized with values less than the threshold as black and values equal to or greater than the threshold as white. 2 The ratio of the total area of black areas of this size or larger is defined as the black area ratio.
2. The gas barrier film according to claim 1 , wherein the resin substrate contains an antiblocking agent.
3. 3. The gas barrier film according to claim 1, wherein the undercoat layer has a thickness of 0.01 to 1 μm.
4. The underlayer contains an organic polymer as a main component, The gas barrier film according to any one of claims 1 to 3, wherein the organic polymer comprises at least one of a polyacrylic resin, a polyol resin, a polyurethane resin, a polyamide resin, and a reaction product of these resins.
5. The gas barrier film according to any one of claims 1 to 4, wherein the inorganic oxide layer has a thickness of 1 to 200 nm.
6. The gas barrier film according to any one of claims 1 to 5, wherein the inorganic oxide layer is aluminum oxide or silicon oxide.
7. The gas barrier film according to any one of claims 1 to 6, wherein the oxygen barrier coating has a thickness of 0.05 to 1 µm.
8. The gas barrier film according to any one of claims 1 to 7, wherein the oxygen barrier coating is a coating comprising at least one of a metal alkoxide, a hydrolysate of a metal alkoxide, and a reaction product of a metal alkoxide or a hydrolysate of a metal alkoxide, and a water-soluble polymer.
9. 9. The gas barrier film according to claim 8, wherein the oxygen barrier coating comprises at least one of a silane coupling agent, a hydrolysate of a silane coupling agent, and a reaction product of a silane coupling agent or a hydrolysate of a silane coupling agent.
10. The gas barrier film according to any one of claims 1 to 7, wherein the oxygen barrier coating contains a polyvalent metal salt of a carboxylic acid which is a reaction product between a carboxy group of a polycarboxylic acid polymer (A) and a polyvalent metal compound (B).
Citation Information
Patent Citations
Lowering of melt viscosity of liquid crystal polymer
JP1986091221A
Gas barrier film
JP1997150484A
Vapor-deposited film laminated packaging material
JP2000254994A
Gas barrier film, and back protection sheet for solar cell using the same
JP2012240222A
Transparent gas barrier laminate
JP2012250470A